Dietary rosemary-derived triterpenic acids enhance growth performance, antioxidant capacity, innate immunity, hypoxia resistance, and tissue integrity in pacific white shrimp (Litopenaeus vannamei) - Rui Feng; Xiaomin Li; Xianyu Chen; Xuanqi Chen; Zhihao Zhang; Handi Wu; Jinlin Chen; Sihan Lin; Zhihong Liao; Wei Zhao; Jin Niu (Aquaculture, 2027)

Introgression shapes the genomic conflict landscape of Malus, providing evidence for a reticulate backbone in a woody crop lineage - Xiao-Ya Li; Zhao-Qian Niu; Ya-Wen Zheng; Jue-Lin Huang; Dai-Kun Ma; Jia-Xin Huang; Qiang Hao; Ti-Cao Zhang; Si-Yu Xie; Chao Xu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2026)

The novel approach for realizing carbon neutrality of coal: backfill material-assisted CO2 sequestration in UCG combustion cavities - Lin Xin; Lingran Min; Min Yang; Shuqin Liu; Weimin Cheng; Maofei Niu; Ruonan Wang; Tongtong Diao (Fuel, 2026)

Processing-driven structure-activity relationships of Polygonatum rhizome polysaccharides: From traditional processing to microbial fermentation - Mengshi Xiao; Zhili Yu; Jiuxiang Nie; Yuping Wei; Lin Zhang; Haijin Mou; Qiuhong Niu (Food Research International, 2026)

Infectious spleen and kidney necrosis virus promotes replication organelle formation and sphingolipid biosynthesis to facilitate viral replication - Wenwen Xiao; Xiaozhe Fu; Yilin Zhu; Qiquan Liu; Qiang Lin; Hongru Liang; Xia Luo; Yinjie Niu; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2026)

Durable and efficient 2D/3D perovskite bulk heterojunction solar cells via BA2MAPb2I7 single crystal addition - Zihong Cai; Xin Chen; Zixing Guo; Yafei Wang; Tianqi Niu; Junyu Lin; Shihai Ye; Qianqiu Guan; Jiazhen Xu; Jiale Huang; Tao Zou; Zuoshan Zhang; et al. (Chemical Engineering Journal, 2026)

Fold-crease induced paper wicking enhancement enabling rapid and high-yield plasma separation - Xianchang Wu; Tonghuan Zhan; Fuzhou Niu; Yange Huang; Heng Wang; Lin Hu; Bing Xu (Analytica Chimica Acta, 2026)

Biomass steam gasification over La-Ce-modified dolomite-based porous ceramics: Hydrogen-rich gas production and tar conversion - Yong-hong Niu; Zheng-yang Chi; Yi-fei Shi; Lin Ma (Sustainable Chemistry and Pharmacy, 2026)

An LLM-based framework with multi-scale temporal disentangling and scale-wise learnable prompt alignment for influent ammonia nitrogen forecasting - Zhixin Li; Danxia Li; Jinrong He; Zhirui Niu; Zheng Liu; Zhihua Feng; Caiyan Lin (Journal of Water Process Engineering, 2026)

Three-dimensional reconstruction reveals distinct endodermal network topology associated with root ion transport characteristics in balsa - Taining Pei; Jinyuan Xiong; Hongxia Lin; Yuqian Zhang; Jiangming Wang; Qian Niu; Xi Zhang; Xiaojuan Li; Yuanyuan Zhao (Journal of Plant Physiology, 2026)

Unravelling extracellular electron transfer kinetics: Microbial responses to interfacial chemistry in bioelectrochemical systems - Shuang Wang; Chun Hong Mak; Shella Permatasari Santoso; Wenxin Niu; Jiun-Tai Chen; Chunyan Tan; Ji-Jung Kai; Carol Sze Ki Lin; Hsien-Yi Hsu (Journal of Environmental Chemical Engineering, 2026)

Ecotoxicity of Folsomia candida induced by 1,2,4-TCB: Insights from multi-level experiments and molecular simulations - Ronghua Du; Jixian Feng; Xue Niu; Xianglong Lin; Fei Guo; Fengchang Wu (Journal of Environmental Sciences, 2026)

Processing of watermelon seed shells nanocellulose with electron beam irradiation and esterification modification: Consequences on fundamental characteristics, molecular structure, physicochemical properties, functional performance, and associated mechanisms - Hanlin Guan; Li Niu; Qian Lin; Xiangrui Ren; Wenqing Zhao; Wei Liang; Yayun Hu; Wenhao Li (Food Chemistry, 2026)

Microplastics as pathway-selective modulators rewire nitrogen cycling in coastal wetlands: Polymer identity outweighs concentration - Dan Wang; Niu Li; Jining Shao; Xingna Lin; Youzheng Zhang; Wenting Cao; Xuexin Shao; Ming Wu (Environmental Pollution, 2026)

Mechanochemical engineering of interfacial M-Ov-Ni sites in CeZrO/Ni catalysts for reinforced low-temperature CO2 methanation - Xiaopo Niu; Yeben Liu; Yining Xia; Xinyu Hu; Zhengguo Wang; Chuqiao Song; Quanli Ke; Xiaoli Wei; Guokai Cui; Qingfa Wang; Lili Lin; Hanfeng Lu (Chemical Engineering Journal, 2026)

Synergistic multi-electron/proton transfer in Cu4POM@MOF composite boosts ammonia generation - Ning Gong; Shuyu Li; Linhua Wang; Xiaotian Wu; Ge Chen; Guangyang Liu; Luming Yang; Yi Niu; Liao-Yuan Yao; Donghui Xu; Lin Qin (Chemical Engineering Journal, 2026)

A universal chemical strategy towards the use of diluent for carbonate localized high-concentration electrolytes - Qingjiang Liu; Min Niu; Xingyu Chen; Zongfan Yang; Yan Meng; Yi-Bing Wang; Xian-Xin Feng; Liwei Dong; Lin Mei; Libao Chen; Changsong Dai; Bo Song; et al. (Chemical Engineering Journal, 2026)

Biomimetic 3D-printed porous root-analogue implants: Overcoming stress shielding, enhancing osseointegration and promoting soft tissue sealing - Yaqi Hao; Shaojie Dong; Changquan Shi; Jinlong Yang; Jingning Gou; Chuncheng Yang; Chaozong Liu; Lin Niu (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

A Dual-Driven Mineral Prospectivity Model and Ternary Ore-Control Framework in Guangxi, Southwest China - Lihao Feng; Qingfei Wang; Daniel D. Gregory; Lin Yang; Yunyun Niu; Hesen Zhao (Natural Resources Research, 2026)

Biodegradation of cyano liquid crystal monomers by an aerobic enrichment culture: Key degraders and interspecies synergistic mechanisms - Minghan Zhu; Chang He; Shaoyu Tang; Jiayu Zhang; Zhen Yu; Hui Lin; Yibo Yuan; Jonathan W.C. Wong; Hua Yin; Junfeng Niu; Xujun Liang; Zhi Dang (Water Research, 2026)

Sustainable nitrogen-doped biochar derived from dual agricultural wastes for water treatment - Feihuang Lin; Jiewen Wu; Zhantu Zhang; Yuyuan Zhang; Chenlong Niu; Jifeng Cui; Menglei Chang; Haoran Yuan; Huawen Hu (Journal of Water Process Engineering, 2026)

Evolution and mechanisms of tidal duration asymmetry in the Xijiang River Channel of the Pearl River Estuary - Xianzhao He; Shuai Hu; Xiangyuan Li; Haichen Liu; Min Gao; Jianliang Lin; Xiaohe Zhang; Lixia Niu; Qingshu Yang (Journal of Hydrology, 2026)

Intelligent mining of generation operation rules for cascade hydropower reservoirs driven by large language models and knowledge graphs - Zhong-kai Feng; Teng Lin; Wen-jing Niu; Yang Xiao; Tao Yang; Hongwu Tang (Journal of Hydrology, 2026)

Discrimination of gold deposit types based on big data analysis and machine-learning techniques - Lihao Feng; Qingfei Wang; Daniel D. Gregory; Lin Yang; Yunyun Niu; Guodong Zhu; Huajian Li; Hesen Zhao; Weijun Weng (Journal of Asian Earth Sciences, 2026)

The role of ion valence in hydrogen production and wastewater decolorization driven by reverse electrodialysis - Qiang Leng; Feilong Li; Yuelong Niu; Ziyun Song; Xiuzhen Li; Jiangli Wang; Lin Wang; Xi Wu (Fuel, 2026)

Regulation of rice bran physicochemical properties, bioactive components and functional properties by synergistic fermentation of Bacillus subtilis and Aspergillus niger - Wenqing Zhao; Jiahui Zhou; Qian Lin; Xiangrui Ren; Li Niu; Wenhao Li (Food Bioscience, 2026)

A species-specific QSAR-based framework for PFAS hazard identification and ecological risk mapping - Weigang Liang; Jingya Li; Lin Niu; Xiaolei Wang; Xiaoli Zhao (Environmental Research, 2026)

Mechanically robust and highly conductive hydrogels with synergistic cross-linking networks for flexible supercapacitors - Zhixin Shen; Jian Lin; Xiao Lian; Kaixuan Wang; Helin Niu (Chemical Engineering Journal, 2026)

Mapping Whole-Brain Nonlinear Structure-Function Dynamics in Aging via Neural Granger Causality - Meng Niu; Shanli Ren; Chen Lin; QingChen Wang; Yongzhi Yin; Hanning Guo; Yu Fu (Brain Topography, 2026)

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Extreme precipitation during the warm growing season amplifies methane emissions and reduces non-growing season contributions in a Tibetan alpine peatland - Zhenrong Lin; Zhirang Wu; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; Shaoying Wang; Xianhong Meng; Ruijun Long; Lei Ma (Agricultural and Forest Meteorology, 2026)

Experimental study on an improved debris-flow dewatering brake using permeable asphalt concrete and a method for predicting its mitigation effectiveness - Chuke Meng; Zhipan Niu; Pengzhi Lin; Yujian Ye; Li Tao; Weiyang Zhao (Bulletin of Engineering Geology and the Environment, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Wave climate characteristics and long-term trends in the northern South China Sea: A 31-year hindcast study for offshore engineering applications - Jinzong Guan; Qianru Niu; Yanqing Feng; Yan Li; Xiaomei Liao; Lin Mu (Ocean Engineering, 2026)

Microwave co-pyrolysis of oily sludge and corn stalk under different microwave absorbents - Jiantao Li; Zhenlin Xie; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Fawei Lin; Guanyi Chen (Journal of Hazardous Materials, 2026)

Machine learning uncovers tidal DOM transformations and keystone molecules via FT-ICR MS and reactomics for estuarine nutrient cycling - Guosheng Zhao; Longfei Wang; Yi Li; Jiaying Chen; Lihua Niu; Li Lin (Journal of Environmental Sciences, 2026)

Temperature and osmotic pressure dual-stimuli-responsive ophthalmic gels embedded with HPCD-modified nanoparticles for prolonged-release delivery of natamycin - Bixia Lin; Fangfei Fan; Hui Xu; Xin Li; Yufei Li; Chunya Qin; Xiaoyun Zhang; Shiqiang Zhang; Yang Gao; Lirong Niu (Drug Delivery and Translational Research, 2026)

Closing the loop with generative AI and automated experimentation in electrochemical energy innovation - Zhiqiang Niu; Wanhui Zhao; Lisa Jackson; Qiong Cai; Valerie J. Pinfield; Wen-Feng Lin; Billy Wu; Kun Luo; Yun Wang (Science Bulletin, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Rational design of antibacterial and biodegradable PCL/oxidized cassava starch/Nisin ternary films based on molecular docking - Xiangrui Ren; Li Niu; Liping Zhao; Wenqing Zhao; Qian Lin; Shuangfeng Guo; Yayun Hu; Wenhao Li (Journal of Food Engineering, 2026)

Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Heterodimeric prodrug nanoassembly overcomes chemoresistance and ignites immunotherapy in glioblastoma - Guanting Li; Shunzhe Zheng; Penghui Wei; Haonan Li; Meixiu Lu; Xuegang Niu; Jiebo Li; Huimin Wang; Wen Huang; Chenyu Ding; Yuanxiang Lin; Yang Zhu; et al. (Chemical Engineering Journal, 2026)

Autophagy attenuates the secondary senescence of endometrial stromal cells induced by Bisphenol S - Xuguang Mi; Jianhua Fu; Lei Liu; Lingshan Wang; Shiling Chen; Mengxue Wu; Chunxue Niu; Yan Wang; Lixin Cao; Lin Wang; Ling Deng; Xiaodan Lu; et al. (Chemico-Biological Interactions, 2026)

The antimicrobial arsenal of endophytes in Lilium pumilum: active components of Fusarium tricinctum and antifungal mechanisms - Yong-Jiao Niu; Lin-Bo Liu; Zhong-Duo Yang; Cui-Juan Xu; Tian-Kun Zhao; Lei-Lei Chen; Qian-Qian Wang; Bing Sun; Sahyun Kim (Archives of Microbiology, 2026)

An Rnf213-deficient hypoperfusion model reveals Moyamoya-relevant neurovascular remodeling - Yuanyuan Dai; Xiaoxin Wu; Shuai Li; Xingyang Niu; Jiaoxing Li; Jianhao Lin; Wenli Sheng (Angiogenesis, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Overlooked spectral matching-Enabled sulfoxide wastewater valorization and in situ pollutant elimination - Lingzhi Shen; Yue Yang; Yixun Zheng; Mengyang Niu; Zhiqing Lin; Zihong Xu; Yongpeng Zhang; Shan Yao; Yanli Wang; Kun Zhao; Zhenjun Xiao; Zili Lin; et al. (Journal of Cleaner Production, 2026)

Degradation performance and mechanism of pyridine and 2-diethylamino-4‑hydroxy-6-methylpyrimidine by Pandoraea captiosa HR2 in individual or simultaneous systems - Hongyu Niu; Wencong Lin; Songyan Zhu; Weitao Liu; Shiqiang Tian; Haijun Yang; Rilong Zhu (Journal of Environmental Sciences, 2026)

Domestic and exotic freshwater fish communities of different water systems under anthropogenic pressures: Diversity patterns, environmental drivers and ecological interactions - Peixuan Wang; Nan Yang; Xiaodong Hu; Lihua Niu; Jixiong Xu; Rui Huang; Li Lin; Yi Li (Journal of Environmental Sciences, 2026)

Film matrix modification synergize with active ingredient introduction strategy to synthesize polysaccharide-based active packaging with enhanced barrier performance and functional activity for efficient perishable fruit preservation - Zitian Liu; Ligang Lin; Jiaxin Zhang; Kui Niu; Minglun Cheng; Yuxuan Zhu; Bin Du; Wenlong Hou; Huiyang Shang (Food Hydrocolloids, 2026)

Functional characterization of fungal laccases via siRNA silencing enables targeted biodegradation - Jiaqi Sun; Lianyan Yuan; Mengna Niu; Ping Xu; Jinsheng Lin; Cuixin Li; Lin Ma; Huiping Li; Qiang Wang; Shaoxuan Qu (Environmental Pollution, 2026)

Trophic transfer in a cold seep food web: Dual constraints from δ13C-δ15N isotopes and rare earth elements - Zice Jia; Niu Li; Xun Sun; Shamik Dasgupta; Shaomin Lin; Hongfei Lai; Wenhua Feng; Chao Zhong; Zenggui Kuang; Fang Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Linking dissolved organic matter sources to greenhouse gas potential in thermokarst lakes of the Qinghai–Tibet Plateau - Wenyan Liu; Zeyong Gao; Chengming Zhang; Fujun Niu; Yibo Wang; Zhanju Lin; Youhua Ran; Jing Luo; Guoan Yin; Yunhu Shang (Cold Regions Science and Technology, 2026)

Initial assessment Himawari-9 AHI aerosol optical depth over land - Hao Lin; Qingxin Wang; Jiqiang Niu; Jie Yang; Wenqiao Li; Shengpeng Liu (Atmospheric Pollution Research, 2026)

Genetic diversity of passion fruit germplasms analyzed by using start codon targeted (SCoT) markers - Jiaqi Zhang; Zhenjie Zhang; Yunqi Xu; Qingqing Zhu; Yulan Zhang; Zeyao Lin; Sihao Wu; Qiujin Lin; Li Jiang; Lijun Du; Zongqiang Shi; Xianqian Niu; et al. (Genetic Resources and Crop Evolution, 2026)

Improving growth performance across multiple sheep breeds by targeting the MSTN gene using an enhanced Cas12i system - Bo Liu; Huanyu Song; Miao Yan; Yu Wu; Pengfei Li; Zhanqing Fan; Yufei Chen; Yangsheng Wu; Jiapeng Lin; Liqin Wang; Xiaoyu Niu; Kun Xu; et al. (Science China Life Sciences, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Enhanced anaerobic digestion of stranded Enteromorpha via combined desalination and disruption pretreatment: Unveiling the kinetic, mechanistic, and microbial community assembly principles - Wenshan Huang; Yue Wu; Junpeng Qiao; Feiyang Lin; Jixin Su; Qigui Niu (Journal of Water Process Engineering, 2026)

Optimizing water-nitrogen management mitigates GHG emissions: microbial mediation across soil oxic and hypoxic interfaces - Yunyu Wu; Shurong Hao; Yi Li; Lihua Niu; Congyi Liu; Li Lin (Journal of Cleaner Production, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Multi-scale insights: Impact of drying on water status, antioxidant mechanisms, and phenolic metabolomics in Osmanthus fragrans var. thunbergii - Xiangrui Ren; Temirlan Khamiddolov; Li Niu; Qian Lin; Wenqing Zhao; Yìxiang Liu; Wenhao Li (Food Research International, 2026)

Modulating molecular assembly behavior of myosin under freeze-thaw treatment using EGCG for improving gel and physicochemical properties at low ionic strength - Xi Zhou; Zhichao Xiao; Yatong Wang; Jianmei Zheng; Laixue Ni; Xianqi Yao; Lin Chen; Xianchao Feng; Yabin Niu (Food Research International, 2026)

Elucidating the effects of E-beam pre-irradiation on the Chinese safflower (Carthamus tinctorius L.): From a structure, active components, and antioxidant capacity perspective - Wenqing Zhao; Xiangrui Ren; Wei Niu; Qian Lin; Yayun Hu; Kui Li; Wenhao Li (Food Chemistry, 2026)

Electrostatic bridging of glycyrrhizic acid to enhance the properties of Pickering emulsion gel stabilized by cinnamaldehyde-tannic acid-chitosan particles - Zijin Sun; Jingxian Niu; Baicun Chen; Hangyan Ji; Chao Qiu; Qianzhu Lin; Zhengyu Jin (Food Bioscience, 2026)

Lysine-directed construction of Co3O4/CeO2 interfaces for enhanced and energy-efficient catalytic styrene oxidation - Yidian Lin; Yinye Chen; Kui Niu; Jing Xu; Yuan Hu; Jiachang Zuo; Shuai Wang; Yongjin Luo; Qingrong Qian; Qinghua Chen (Chemical Engineering Journal, 2026)

Thermal comfort on the move: Understanding thermal alliesthesia on urban walking routes - Yichun Li; Xianzhun Zhong; Yongxin Xie; Richard de Dear; Shuai Lu; Borong Lin; Jianlei Niu (Building and Environment, 2026)

Deciphering osmotic stress responses: a comparative analysis of mechanisms in Gram-positive and Gram-negative bacteria - Jun Liu; Zhigao Liao; Ling Chen; Zhiyu Hu; Xianhao Ouyang; Hong Huang; Yanan Niu; Jin Lin; Jiaxin Chen; Zhengyuan Hu; Chengbin Zhu; Peng Liu; et al. (Archives of Microbiology, 2026)

Integrated Transcriptomics and Machine Learning Reveal Lipid Metabolism Related Genes in Ischemic Stroke - Qiu-Lin Wang; Chang-Le Fang; Tian-Hao Bao; Rui-Ze Niu (Journal of Molecular Neuroscience, 2026)

Metabolomics reveals GABA as a key mediator of salinity stress in razor clam - Geqi Gao; Zihan Lin; Yuting Han; Mengwei Shang; Jiahui Sun; Donghong Niu; Jiale Li (Aquaculture, 2026)

Hydrogeochemical properties and health risks of high-fluoride groundwater in southern Jiaolai Basin - Menghan Tan; Zongjun Gao; Jiutan Liu; Bing Jiang; Linlin Lin; Qiang Li; Yiru Niu (Process Safety and Environmental Protection, 2026)

Impact of extreme rainstorm on the stability of biological activated carbon in drinking water treatment: Differential microbial responses in new versus aged filters - Jia Niu; Haibing Wang; Yue Wang; Tian Lin; Rongxing Lan; Lihong Chen; Xianhua Liu; Kaiqin Xu; Xiaochen Chen; Xiaoyun Wang (Journal of Water Process Engineering, 2026)

Insights into the molecular transformation pathways of humus during co-composting of bagasse pith and buffalo manure using compound microorganisms (LXB) - Shiyuan Niu; Binfeng Lin; Yu Zhang; Hongquan Xiang; De Ding; Zhi Huang; Jianbin Li (Journal of Environmental Chemical Engineering, 2026)

Fe(III)-enhanced degradation of para-nitrophenol in a UV/monochloramine system: Mechanism and toxicity analysis - Niu Ge; Yuyang Mao; Lin Deng; Changbo Zhang; Rajendra Prasad Singh (Journal of Environmental Management, 2026)

Co-addition of alkali lignin and microbial agents drives humic substances assembly by regulating precursor conversion and microbial metabolism in composting - Hongquan Xiang; Shiyuan Niu; De Ding; Binfeng Lin; Yu Zhang; Yongwei Zhu; Shiqiang Li; Ziyang Zhao; Jianbin Li; Zhi Huang (Journal of Environmental Chemical Engineering, 2026)

Source analysis of atmospheric ozone in a typical industry city: Highlighting the role of coal chemical industry in ozone formation - Dongmei Hu; Qiuhong Tao; Yueyuan Niu; Yulong Yan; Wen Yan; XingXiao Gong; Lin Peng (Journal of Environmental Sciences, 2026)

Biopolymer-based edible film incorporating Melaleuca Bracteata F. Muell. Essential oil with antimicrobial and antioxidant properties: A promising approach for strawberry fruit preservation - Jinjie Yang; Yaqian Niu; Penghui Hu; Yunqing Song; Ruihan Dang; Linke Li; Yuke Zhang; Yanshu Gong; Yixuan Lin; Ying Xin (Food Research International, 2026)

A data informativeness evaluation method for grey-box modeling of building thermal dynamics - Xinyi Lin; Zhe Tian; Adrian Chong; Yakai Lu; Jide Niu; Na Deng (Energy and Buildings, 2026)

Achieving 17.65% efficiency in organic solar cells by neutral linker engineering in dimerized small-molecule acceptors - Jianan Niu; Xue Zhou; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Cheng Sun; Tan Wang; Mingliang Sun; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Aconiti Lateralis Radix Praeparata active ingredients of Heishunpian potential on LPS-induced Nrf-2/NQO1/HO-1 and Smad3/Akt/p38 signalling pathways in chronic obstructive pulmonary disease: a network pharmacology study - Yingzhe Wang; Xiyan Niu; Jie Guo; Lin Jia; Qian Liu (Journal of Molecular Histology, 2026)

Gene Regulatory Networks Controlling Fruit Anthocyanin Accumulation: A Review - Da Zhang; Bowei Zhu; Xin Liu; Han Wang; Guodong Zhao; Lin’guang Jia; Dongmei Chen; Tongsheng Zhao; Gang Niu; Chaohong Zhang; Xinsheng Zhang (Applied Fruit Science, 2026)

Evaluating the Shanghai Typhoon Model against State-of-the-Art Machine-Learning Weather Prediction Models: A Case Study for Typhoon Danas (2025) - Zeyi Niu; Wei Huang; Yuhua Yang; Mengqi Yang; Lin Deng; Haibo Wang; Hong Li; Xu Zhang (Advances in Atmospheric Sciences, 2026)

Characteristics of phosphorus-solubilizing bacteria and mediated phosphorus cycle in sediments of urban river-lake interfaces - Yi Li; Xiaoxi Li; Lihua Niu; Jiaxin Hu; Wenlong Zhang; Li Lin; Wenming Zhang (Water Research, 2026)

Hydrodynamics regulates microbial degradation of microplastics by modulating bottom-up and top-down effects in a river-lake confluence zone - Yamei Chen; Yi Li; Lihua Niu; Hans-Peter Grossart; Yingjie Wang; Xin Ma; Li Lin (Water Research, 2026)

In situ biofilm development on microplastics and its impact on PFAS adsorption in aquatic environment - Guoqing Hou; Rui Zhang; Tianhui Zhao; Mengyuan Fang; Lin Niu; Qitao Lei; Qiang Li; Nuo Chen; Zhi Tang; Xiaoli Zhao; Fengchang Wu (Water Research, 2026)

African swine fever virus pNP419L inhibits host translation and increases viral replication through the PERK/eIF2α pathway - Xueying Wang; Zixuan Wang; Yilin Guo; Sai Niu; Rui Liang; Lin Cheng; Hakimeh Baghaei Daemi; Guiqing Peng (Veterinary Microbiology, 2026)

Durability analysis of using MICP to address dispersive soil issues in seasonal freezing areas - Xiaoqing Yuan; Yuhui Wu; Cencen Niu; Xiaolong Yang; Sen Lin; Zeju Wu; Qing Wang; Hui’e Chen; Xin Xu; Hua Du (Soil and Tillage Research, 2026)

Local reaction-global diffusion unlocks high-performance Mg3(Sb,Bi)2-based thermoelectrics - Zhen Fan; Yi Wang; Tenglong Lu; Xiaofan Zhang; Jiawei Yang; Kaiwei Guo; Joseph Woods; Gang Wang; Xiaoyan Niu; Qi Zhao; Xiaowei Wu; Fankai Xie; et al. (Science Bulletin, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Influence of N and P co-statuses on multi-trophic planktonic communities of shallow lakes: Structure, assembly, and energy flow - Lihua Niu; Yalong Zhang; Yi Li; Xiaodong Hu; Xing Hou; Rui Huang; Li Lin (Journal of Environmental Sciences, 2026)

Octenylsuccinic acid modification promotes starch lecithin complexation: Application to the preparation of oleogels - Xinyu Wang; Qian Lin; Li Niu; Wenqing Zhao; Qi Zhao; Ruijie Li; Wenhao Li (Food Hydrocolloids, 2026)

Dual-halide solid electrolyte interphase engineering with MXene enables dense (110)-oriented Li deposition for high-performance Li metal anodes - Zongyu Mao; Shuaihe Zhang; Ye Han; Yujing Xu; Shuxin Xie; Bei Huang; Shuaihong Chen; Xintong Cai; Junyu Lin; Xiao Yu; Shaozhong Zeng; Dongju Fu; et al. (Chemical Engineering Journal, 2026)

Discrepancies in microbial nitrogen cycling among diverse karst hydrological systems: enhanced nitrate reduction potential in karst conduits - Danni Zhu; Yi Li; Lihua Niu; Changsong Zhou; Lianjie Fan; Haiping Lu; Li Lin (CATENA, 2026)

Drier year exhibits amplified promoting effects of shrub encroachment on methane uptake in Tibetan alpine meadows - Lili Nan; Zelong Zhang; Dezhao Gan; Huinan Li; Dongsheng Yu; Zhenrong Lin; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; et al. (Agricultural and Forest Meteorology, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

Biomass ratio regulates methane conversion and carbon fixation in a methanotrophs-microalgae symbiotic system: Efficiency optimization and mechanisms driven by co-metabolism - Xiaoqian Li; Xiao Lin; Ziyi Dong; Rui Zhou; Qigui Niu (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Food waste treatment by black soldier fly larvae (BSFL) and pilot-scale aerobic composting of the BSFL frass using horizontal mechanical reactor - Kailiang Shen; Lulu Liu; Yulong Niu; Yue Chen; Feiran Wang; Yuliang Chen; Lin Lin; Seinn Lei Aye; Zhigang Liu; Deli Wu; Xiaowei Li (Process Safety and Environmental Protection, 2026)

Vegetation responses to the mid-Holocene abrupt climate events in the Forest-Steppe Ecotone in northern China - Yao Zhang; Lili Niu; Qiaoyu Cui; Yi Lin; Zhiping Zhang; Jiaju Zhao; Xinwei Yan; Aifeng Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Comparative study by microwave, fixed-bed and rotary kiln pyrolysis of oily sludge: Petroleum hydrocarbons, N-/S-/Cl-containing pollutants and heavy metals - Jiantao Li; Hongdi Yu; Fawei Lin; Shupeng Zhang; Zizhen Niu; Zhihua Liu; Rui Zhang; Guijian Liu; Xiaojiang Shen; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Streptococcus thermophilus: A next-generation chassis for customizing exopolysaccharide with rare sugar - Mengshi Xiao; Jiuxiang Nie; Xiaodan Fu; Lin Zhang; Haijin Mou; Qiuhong Niu (Food Research International, 2026)

Substrate-enhanced allometric growth of Phragmites australis improved tailwater purification efficiency in constructed wetlands - Tian Lin; Jia Niu; Weipeng Zhou; Huanlong Bai; Lihong Chen (Ecological Engineering, 2026)

Effects of tidal flat reclamation on dissimilatory nitrates reduction processes in an Estuarine wetland - Yanshu Wang; Dengzhou Gao; Chenqingfeng Gao; Jingwen Zhao; Xuyan Niu; Qingyan Wang; Xiaoqian Yu; Jiayi Wang; Ruisi Zheng; Wei Du; Xianbiao Lin (Agriculture, Ecosystems & Environment, 2026)

A monogamous male's dilemma: Managing two females and parental care in white‐faced plovers - Boya Xie; Xi Lin; Xiaotong Niu; Heiman Ho; Xinlei Liu; Xin Lan; Zitan Song; Yachang Cheng; Yang Liu (Ecology, 2026)

Hydro-sedimentary conditions shape the microplastic occurrence in sediments of the Pearl River Estuary (China) - Siyue Zhao; Yuxi Tian; Yuhang Zhong; Jianliang Lin; Lixia Niu; Qingshu Yang (Marine Pollution Bulletin, 2026)

Unveiling decrosslinking degree on polyamide nanofiltration membranes: Structure–performance relationship and micropollutant removal - Xiaozhen Lu; Lin Wang; Xuewu Zhu; Liping Qiu; Zhe Yang; Daliang Xu; Jiashuai Wei; Qianxin Zhang; Chunzhao Chen; Shan Niu; Bin Liu (Water Research, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Ascorbic acid-assisted heterogeneous activation of persulfate by natural pyrite for Microcystis aeruginosa removal - Xiaoxian Zheng; Xiaojun Niu; Xingyao Ye; Dongqing Zhang; Yimin Chen; Lujia Zheng; Huizhen Huang; Yanhuan Lin (Journal of Water Process Engineering, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Atom-level tuning of Co single-atom catalysts to regulate the peroxymonosulfate activation pathway for wastewater remediation - Lin Niu; Qitao Lei; Zhi Tang; Weigang Liang; Yifan Dong; Xiaoli Zhao; Fengchang Wu (Journal of Hazardous Materials, 2026)

Electrochemical detection and electro-Fenton degradation of fipronil via Fe/Ni-BTC/MS-derived NiFe2O4@C core-shell catalyst - Yu-Qing Zhan; Cheng-Guo Liu; Jia-Jia Kou; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Journal of Cleaner Production, 2026)

Oxygen doping regulates coordination structure of iron-single-atom catalysts for peroxymonosulfate activation and pollutants degradation: high-valent iron-oxo species role - Lin Niu; Qitao Lei; Zhi Tang; Yaqi Cai; Junyu Wang; Guoqing Hou; Xiaoli Zhao; Fengchang Wu (Chemical Engineering Journal, 2026)

A meta-plasmonic biosensor for minimal protein interference profiling of serum extracellular vesicles enables high-specific discrimination of liver cancer subtypes - Jiaheng Zhu; Shaowei Lin; Baichang Deng; Jiaqing Shen; Lihuang Zeng; Qiang Niu; Tianhao Huang; Xinyue Huang; Mengqi Jiang; Wei Chen; Yinong Xie; Annuo Chen; et al. (Chemical Engineering Journal, 2026)

Decadal variations in the northern boundary of permafrost in the Xidatan region of the Qinghai-Xizang Plateau: Insights from InSAR and field monitoring - Ju Xin; Luo Jing; Niu Fujun; Yu Fan; Ding Zekun; Yin Guoan; Lin Zhanju; Gao Zeyong (Cold Regions Science and Technology, 2026)

Distribution characteristics of secondary embankment diseases in permafrost regions of Qinghai Province and their relationship with local factors - Peng Zhang; Lei Liu; Yangyang Xie; Xuyang Wu; Xingwen Fan; Wenjiao Li; Nuocheng Li; Xuhui Wang; Fujun Niu; Zhanju Lin (Cold Regions Science and Technology, 2026)

Study on the durability and microstructure evolution of modified concrete in high altitude cold region - Ziyi Wang; Fujun Niu; Zhanju Lin; Yuru Wang; Xinlong Du; Wenyan Du (Cold Regions Science and Technology, 2026)

Creating inbred lines for heterosis utilization in alfalfa - Tengfei Liu; Lulu Li; Hao Lin; Lifang Niu (Science China Life Sciences, 2026)

Adiponectin Signaling Ameliorates Cognitive Dysfunction in Type 2 Diabetic Mice by Activating the Hippocampal AdipoR2-PPARα/CREB Pathway - Hongyan Gong; Yanli Liu; Liu Xia; Bochao Niu; Jian Kong; Bin Wang; Xu Lin; Lin Lin; Yanlin Bi (Molecular Neurobiology, 2026)

Widespread weakening of soil-atmosphere thermal coupling and its response to climate warming on the Qinghai-Tibetan plateau - Guoan Yin; Xin Ju; Fujun Niu; Zhanju Lin; Jing Luo; Zeyong Gao; Hongye Yan; Yanhe Wang; Weiheng Ni (Agricultural and Forest Meteorology, 2026)

Monthly Soil Respiration in China's Forests: Spatiotemporal Patterns and Drivers Over 21 Years - Jiaming Chang; Ni Huang; Li Wang; Luying Zhu; Xiaoyu Lin; Jie Liu; Zheng Niu; Dewen Cai (Global Change Biology, 2026)
Forests play a critical role as terrestrial carbon sinks in mitigating climate change. However, accurate quantification of soil respiration ( R s )—the primary CO 2 efflux from forests—remains challenging due to existing studies' overreliance on annual‐scale estimates, which obscure fine‐scale spatiotemporal dynamics and key drivers of R s . Here, we developed a 500 m resolution monthly R s dataset for China's forests (2000–2020) using remote sensing data and a geographically weighted machine learning model. A geographically weighted extreme gradient boosting model achieved the highest accuracy in predicting monthly R s ( R 2 = 0.74, RMSE = 0.8 g C m −2 day −1 ). The mean total annual R s from 2000 to 2020 was 2.32 ± 0.09 Pg C year −1 , with summer contributing most and winter least. Annual total R s and seasonal total R s showed significant increasing trends across China's forests from 2000 to 2020, with the strongest increases in southern China's young/middle‐aged natural management forests and plantations. The relationships between R s and its driving factors varied: gross primary productivity (GPP) was the primary driver of annual R s across all forest management and age classes. Seasonally, temperature dominated R s in spring/winter, and GPP dominated summer R s across all forest management and age classes, while precipitation effects varied with management/age classes and season. Our findings highlight the necessity of monthly‐scale analysis and the significant role of forest management and age in modulating R s variability.

Sub-metre surface water mapping using Sentinel-1/2 with integrated super-resolution and deep learning - Jie Song; Jinyan Tian; Lin Zhu; Bingfeng Zhou; Xinyuan Qu; Che Wang; Niu Luo; Zhenxin Zhang; Lin Guo; Mingliang Gao; Xiaojuan Li; Huili Gong (International Journal of Remote Sensing, 2025)

Diversification and differentiation of Stipa species shed light on the regional evolutionary history of the eastern Eurasian steppe - Dongqing Yan; Yanyan Fan; Xiaoru Jiang; Yang Ma; Kejian Lin; Zhenhua Dang; Jianming Niu (Molecular Phylogenetics and Evolution, 2025)

Metamorphic conditions and cooling history of the central Himalayan eclogites: A mineralogy and zircon-titanite-rutile U Pb geochronology approach - Xin Dong; Zuo-lin Tian; Yao-ling Niu; Ze-ming Zhang (Lithos, 2025)

Altitude-driven vehicle particle emission surges: Insights from chemical analysis and machine learning - Zhiwen Jiang; Haomiao Niu; Yujie Wu; Lin Wu; Zhou Xu; Hao Qin; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Advances in thermoelectric coupling catalysis for CO2 reduction: Synergistic mechanisms, catalyst development, and application perspectives - Mengke Niu; Lei Wang; Linjie Cai; Jia Liu; Xuan Lin; Jun Yu; Sam Toan; Zhaoteng Xue; Dongsen Mao (Journal of Environmental Chemical Engineering, 2025)

Hydrocarbon generation and pore evolution in marine organic-rich shales across maturation stages - Xueying Wang; Kun Zhang; Zhenxue Jiang; Yanhua Lin; Yan Song; Chengzao Jia; Shu Jiang; Lin Jiang; Hulin Niu; Jing Li; Yunbo Zhang; Xingmeng Wang; et al. (Fuel, 2025)

Complexation of chitosan-modified porous starch with chlorogenic acid to form ternary gels: Multiscale structural changes and retrogradation behavior - Li Niu; Xiangrui Ren; Hanlin Guan; Xinyi He; Qian Lin; Wenqing Zhao; Wei Liang; Wenhao Li (Food Chemistry, 2025)

Particle number emissions on mountainous roads: machine learning insights from on-road testing - Zhiwen Jiang; Yujie Wu; Lin Wu; Haomiao Niu; Wei Feng; Wentian Xu; Jiawei Yin; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Environmental Research, 2025)

In-situ polymerized ether-ester copolymer electrolytes with regulated solvation structure for quasi-solid-state lithium metal batteries - Guocheng Wang; Yongjie Dan; Xinyu Lin; Qi Liu; Yanhua Niu; Guangxian Li (Chemical Engineering Journal, 2025)

Synergistic selenide-vacancy sites in CeO2/CoSe2/g-C3N4 nanocomposites enabling enhanced Hg0 sequestration from coal-fired flue gas - Yujiang Fan; Qiang Niu; Fenghui Wu; Tao Yang; Yiting Wang; Dandan Chen; Yuanchuan Ren; Xuejun Zhu; Haiying Lin; Minjie He; Bangjin Chen (Chemical Engineering Journal, 2025)

MOF-derived core-shell MnFe2O4@C bifunctional material: Electrochemical sensing and synergistic electro-Fenton degradation of clothianidin - Jia-Jia Kou; Yu-Qing Zhan; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Chemical Engineering Journal, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

Zinc Fertilizer Application in Different Stages Changes the Accumulation and Remobilization of Zinc in Winter Wheat - Muhammad Fraz Ali; Yuxi Niu; Guoming Li; Lijuan Ma; Xiang Lin; Shubo Gu; Yong Han; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Non-coding RNAs-regulated SLC7A11 modulates ferroptosis: a new strategy for cancer therapy - Xinyu Niu; Jiawen Nie; Lijie Zhang; Feng Chen; Zhijuan Lin (Functional & Integrative Genomics, 2025)

Gene expression of long non-coding RNAs and messenger RNAs in Varroa destructor mites exposed to essential oil of camphor leaves - Siyi Shen; Meng Li; Tongyu Dong; Kai Xu; Lili Wu; Kang Wang; Defang Niu; Qingsheng Niu; Ting Ji; Zhi Wang; Zheguang Lin (Experimental and Applied Acarology, 2025)

AlgaeDiff-Net: A novel computational framework for automated microalgae species identification and morphological analysis - Shihuan Luo; Yiheng Niu; Jiayi Tang; Danyan Yang; Xintao Lin; Biwen Yang; Zerong Guan; Yifan Zhou; Huiqing Zhong; Zhiming Liu; Zhouyi Guo (Algal Research, 2025)

Underwater sea cucumber detection based on domain-invariant features - Fangqun Niu; Zejin Liu; Xinyu Zheng; Junyi Wang; Dexuan Zhang; Yuanshan Lin; Xiaoting Zhu; Shuai Yang; Wei Wang; Guodong Li (Aquaculture International, 2025)

Spatial heterogeneity and nonlinear relationship between landscape ecological risk and drivers: a case of the Qinghai-Tibet Plateau, China - Fazi Zhang; Jingyao Lin; Qiang Wang; Yuying Lin; Niu Dang; Yinan Li (Environment, Development and Sustainability, 2025)

Determinants and dynamic mechanisms of microbial communities in mangrove sediments of the qingjiang estuary - Yongjun Luo; Siyue Zhao; Qingbi Tan; Hongying Guo; Jianliang Lin; Huafeng Chen; Jiange Jiao; Hui Nie; Saihua Huang; Lixia Niu (Plant and Soil, 2025)

Engineering scaffold-cell interactions for cultured meat: mechanisms, materials, and emerging AI-driven strategies - Linzi Li; Yijun Zhang; Zipeng Xu; Shuai Yan; Nuo Yan; Cong Zhao; Yabin Niu; Shijie Ding; Guanghong Zhou; Lin Chen; Xianchao Feng (Trends in Food Science & Technology, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Controlling product selectivity and residual carbon behavior in biomass pyrolysis via pulse-structured joule heating - Yang Liu; Ruming Pan; Renaud Ansart; Chenxu Zhong; Yue Niu; Hongdi Yu; Fawei Lin; Gérald Debenest (Process Safety and Environmental Protection, 2025)

Spring-neap variations in tidal duration asymmetry in the Pearl River Estuary: Dominant tidal combinations and long-term evolution - Jianliang Lin; Shuai Hu; Ping Zhang; Linxi Fu; Xianzhao He; Huayang Cai; Lixia Niu; Xiaohe Zhang; Qingshu Yang (Journal of Hydrology, 2025)

Preparation and characterization of ginger essential oil nanoemulsion composite films and its effect on preservation of cherry tomatoes - Peihang Chen; Lijing Lin; Bei Zhang; Qiubian Yang; Jiajia Niu; Sipu Zhang; Jianyin Miao (Food Control, 2025)

Occurrence, spatial distribution, and risk assessment of per- and polyfluoroalkyl substances in soil and groundwater of a petrochemical industrial park in China - Qitao Lei; Lin Niu; Zhi Tang; Yali Shi; Xiaoli Zhao; Yaqi Cai (Environmental Pollution, 2025)

Interface engineering of flower-like ZIF-67 derived CoSe2/g-C3N4 heterojunction for efficient immobilization of elemental mercury - Guanjian He; Yujiang Fan; Qiang Niu; Gelimei Zhang; Fenghui Wu; Dandan Chen; Chun Lv; Jie He; Haiying Lin; Minjie He (Chemical Engineering Journal, 2025)

Microwave-tailored S-scheme MOF@MOF heterojunctions: Synergistic dual-charge transfer and polarization enhancement toward efficient antibiotic degradation - Jiliang Niu; Yuetong Lin; Mianmian Yin; Kaiting Mai; Cheng Qiu; Minling Gao (Chemical Engineering Journal, 2025)

Multi-scale investigation of mechanical properties and solidification mechanisms of diverse cementitious materials for solidifying subgrade talik in permafrost regions - Yuru Wang; Fujun Niu; Ziyi Wang; Zhanju Lin; Minghao Liu (Cold Regions Science and Technology, 2025)

Thermal sensation and comfort models for non-uniform and transient environments, Part V: Enhancements of whole-body sensation model - Junwei Lin; Yan Liang; Junran Yang; Yongxin Xie; Hui Zhang; Jianlei Niu (Building and Environment, 2025)

LINC02266 promotes proliferation and metastasis and inhibits ferroptosis of gastric cancer cells by regulating AKT/ACSL4 pathway - Xiaoru Liang; Xinyu Niu; Lijie Zhang; Chang Liu; Xiaomin Zhao; Feng Chen; Zhijuan Lin (Molecular and Cellular Biochemistry, 2025)

ROV-assisted in situ density estimation for sea cucumbers via lightweight YOLOv8-FA and enhanced ByteTrack - Yanqiang Yang; Haolong Ban; Junyi Wang; Zejin Liu; Fangqun Niu; Qijun Chen; Jiaxu Zhang; Wei Wang; Zhijun Li; Yuanshan Lin (Aquaculture International, 2025)

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

Reducing Aerodynamic Interference Through Layout Optimization of Symmetrically Cambered Wingsails: A Comparative Study of In-Line and Parallel Configurations - Stephan van Reen; Jianfeng Lin; Jiqiang Niu; Peter Sharpe; Xiaodong Li; Hua-Dong Yao (Journal of Marine Science and Engineering, 2025)
Rigid wingsails are increasingly adopted for wind-assisted ship propulsion, with Symmetrically Cambered (SC) profiles identified as highly efficient for thrust generation. This study investigates installation layouts for multiple SC wingsails, focusing on aerodynamic interference that limits their performance. A fast 2D potential-flow panel method is employed and benchmarked against wind tunnel and 3D IDDES data. Two representative layouts are analyzed: triple-in-line (TL) and quad-in-parallel (QP). Layout optimization is performed using a genetic algorithm with distances between sails as design variables, constrained by the total installation span, at apparent wind angles (AWAs) of 60°, 90°, and 120°. Results show that thrust generation decreases progressively from upstream to downstream sails due to interference effects, with penalties of about 4–6% in the TL and up to 28% in the QP layout. The optimization improves performance only for the TL layout at 60°, while the QP layout shows negligible gains. Analysis of pressure distributions confirms that downstream sails suffer from reduced suction on the leading edge caused by upstream wakes. Overall, the TL layout demonstrates significantly higher aerodynamic reliability than the QP layout. These findings provide new insights into multi-sail configurations and highlight the importance of layout optimization in maximizing thrust efficiency.

Human umbilical cord mesenchymal stem cell-derived exosomes repair raloxifene-induced damage in endometrial stromal cells via autophagy activation - Shiling Chen; Xiuying Lin; Lei Liu; Jianhua Fu; Xiaodan Lu; Chunxue Niu; Qilai Wang; HaiFeng Wei; Mengxue Wu; Munan Sun; Lixin Cao; Xuguang Mi; et al. (Reproductive Toxicology, 2025)

Two pairs of isomeric resin glycosides from Argyreia obtusifolia - Shuo Chen; Yi-Lin Niu; Zhi-Tong Li; Hong-Hua Cui; Yong-Qin Yin; Yan-Fen Chen (Phytochemistry Letters, 2025)

Multi-omics approaches provide insights into adaptation to low salinity of intertidal clams - Zihan Lin; Honglei Wang; Geqi Gao; Hongtao Nie; Kai Ye; Donghong Niu; Jiale Li (Marine Environmental Research, 2025)

Hybrid prediction model for multi-step wastewater influent quality using adaptive wavelet denoising and enhanced Informer - Lili Ma; Danxia Li; Jinrong He; Zhirui Niu; Zheng Liu; Zhihua Feng; Caiyan Lin (Journal of Water Process Engineering, 2025)

Unveiling the social and environmental benefits of electric vehicles: A case study of Shanghai - Junjie Chen; Xin Lai; Quanwei Chen; Yuejiu Zheng; Yue Niu; Lin Sun; Bo Tang; E Cheng (Journal of Environmental Management, 2025)

Amphiphilic block copolymer-based fire suppression material – Study on coal spontaneous combustion prevention and extinguishing performance - Gang Zhou; Hongrui Qu; Bo Wei; Tianrui Niu; Yongmei Wang; Xiaosu Dong; Rulin Liu; Lin Li; Shuailong Li (Journal of Environmental Chemical Engineering, 2025)

Exposure assessment of Staphylococcus aureus in fluid milk - Yingying Lin; Mingjie Pan; Yunfeng Yang; Xiao Ye; Huahu Xu; Yikan Lin; Bing Niu (International Dairy Journal, 2025)

Advanced anion exchange membrane for electrodialysis application based on quaternized poly (phthalazinone ether sulfone) - Fanchen Sun; Qian Liu; Zijian Li; Xuefu Che; Lin Zhuo; Yiping He; Guanwen Huang; Kang Niu; Shouhai Zhang; Xigao Jian (Desalination, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Domain generalization for sea cucumber detection: Tackling background color variability in aquaculture settings - Fangqun Niu; Yifan Sheng; Junyi Wang; Xinyu Zheng; Kexin Liu; Yuanshan Lin; Wei Wang; GuoDong Li (Aquaculture International, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Hydrogels with anti-inflammatory modulation microniches for tendon repair - Tao Zhou; Tao Ma; Qiankun Wang; Zifu Wang; Jun Huang; Lin Zhong; Ding Zhou; Zhe Jin; Yang Niu; Dong Yin; Tianyou Hu; Yujie Bian; et al. (Chemical Engineering Journal, 2025)

Data augmentation-based fault diagnosis framework for nuclear power plants with robust anti-data interference capability - Jiangkuan Li; Shangcai Zheng; Jiaoshen Xu; Meng Lin; Zhenfeng Niu; Jiahao Cheng; Chenxin Zhu; Ruifeng Tian; Sichao Tan (Annals of Nuclear Energy, 2025)

Flash: Dual-gradient filtering membranes enable ultra-fast plasma separation - Xianchang Wu; Hui Niu; Tonghuan Zhan; Yulun Wu; Ping Qiao; Lin Hu; Bing Xu (Analytica Chimica Acta, 2025)

A Kinetic Study on the Accumulation of No.0 Fuel Oil and Pinghu Crude Oil Water-Accommodated Fraction in Exopalaemon carinicauda - Lei Li; Yiyun Zhang; Li Wei; Aijia Lin; Jiaying Cai; Zengqiao Wei; Qingyuan Wu; Junxiang Niu; Yanming Sui; Mei Jiang (Fishes, 2025)
The kinetic parameters of No.0 fuel oil and Pinghu crude oil water-accommodated fractions (WAFs) during accumulation and elimination in Exopalaemon carinicauda were quantified using a semi-static two-compartment kinetic model. The accumulation phase data were analyzed via nonlinear regression to obtain kinetic parameters, yielding critical values including the uptake rate constant (k1), elimination rate constant (k2), bioconcentration factor (BCF), equilibrium body burden (CAmax), and biological half-life (B1/2). Modeling results demonstrated distinct kinetic parameters for the two oils. For No.0 fuel oil, the average values were k1 = 5.21; k2 = 0.1105; BCF = 48.98; CAmax = 2.95 mg/kg; and B1/2 = 6.40 days. For Pinghu crude oil, the averages were k1 = 10.25; k2 = 0.1044; BCF = 98.15; CAmax = 8.48 mg/kg; and B1/2 = 6.64 days. The uptake rate constant (k1) and BCF generally decreased with increasing petroleum hydrocarbon exposure concentrations in ambient seawater, while the elimination rate constant (k2) remained relatively constant across different concentrations. CAmax increased proportionally with the petroleum hydrocarbon exposure concentration. Goodness-of-fit tests confirmed that the petroleum hydrocarbon concentrations in the experimental data were well described by the semi-static two-compartment model. Throughout the testing period, the concentration of No.0 fuel oil in Exopalaemon carinicauda remained lower than that of Pinghu crude oil.

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Mineralized-anomaly identification based on potential-enhanced positive-unlabeled bagging: A case study from Guangxi gold ore province - Guodong Zhu; Lin Yang; Yunyun Niu; Qingfei Wang (Journal of Geochemical Exploration, 2025)

Spatiotemporal analysis of illegal Coilia nasus fishing linked to suitable habitats modeled with MaxEnt in China - Suhang Wei; Junjie Zhong; Songyin Qiu; Xiaodong Sun; Mingjie Pan; Yingying Lin; Qin Chen; Bing Niu (Journal for Nature Conservation, 2025)

Insight into the enhancement mechanism of repeated freezing-thawing pretreatment promotes carboxymethylation for improving the properties of sweet potato starch: From a multiscale structural perspective - Li Niu; Siwen Yu; Xinyi He; Wei Liang; Qian Lin; Qi Zhao; Xinyu Wang; Ruijie Li; Wenhao Li (Food Chemistry, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

The impact of season, temperature, and direct normal irradiance on IVF pregnancy outcomes: a retrospective cohort study - Chao Wang; Jiehua Chen; Zhong Lin; Li Shi; Qiuyan Ruan; Jiamin Long; Yanping Lao; Xiangli Niu (International Journal of Biometeorology, 2025)
Objective . This study assessed associations between season, temperature, direct normal irradiance (DNI), and clinical pregnancy outcomes in first fresh in vitro fertilization (IVF) cycle. Methods . We conducted a retrospective cohort study (June 2021-October 2023) of 1179 patients undergoing fresh IVF cycles. Inclusion criteria required age ≤ 45 years, first-time fresh embryo transfer cycles (long/antagonist protocol), excluding preimplantation genetic testing, frozen cycles, or incomplete data. Temperature and DNI were recorded from gonadotropin (Gn) initiation to oocyte retrieval. Binary logistic regression assessed seasonal impacts on clinical pregnancy, while restricted cubic splines (RCS) independently modeled temperature/DNI effects. Results . Compared to winter, clinical pregnancy likelihood was 1.74-fold higher in spring (95% CI:1.11–2.71, P = 0.015) and 1.53-fold in summer (95% CI:1.02–2.30, P = 0.042). Stratified analysis revealed a 2.02-fold increased likelihood in summer cycles using the long protocol (95% CI:1.07–3.82, P = 0.031), whereas no seasonal variation was observed in antagonist protocol. RCS regression analysis indicated a nonlinear relationship between temperature and clinical pregnancy outcomes, which was confirmed in the long protocol group. No significant correlations were observed with DNI or in patients treated with the antagonist protocol. Conclusions . Season and ambient temperature significantly impact IVF clinical pregnancy, especially in the long protocol, with the highest increase in pregnancy rates observed in summer, as well as within the 26.13℃ to 29.68℃ temperature range. No significant effects were observed with DNI or the antagonist protocol. These findings suggest that summer treatment may optimize IVF outcomes, but future studies should prioritize multi-center prospective designs with continuous temperature monitoring to define precise optimal ranges.

A novel method for local clothing insulation prediction to support sustainable building and urban design - Junwei Lin; Ying Jiang; Yongxin Xie; Jianlei Niu (International Journal of Biometeorology, 2025)
Clothing is crucial in thermal comfort evaluation, affecting heat exchange between the body and the environment. Assuming even clothing insulation across body segments can lead to inaccurate predictions, affecting building and urban design strategies. This study processed insulation data from 240 clothing ensembles to derive local insulation values. Regression models were developed to relate local and overall insulation values, allowing fast estimation of local insulation distribution for any given overall value. To validate the effectiveness of local clothing insulation values predicted by the proposed methods, measured real-time skin temperatures were collected from field experiments and compared with predicted values. Results demonstrated a significant accuracy improvement in the predicted local skin temperature from thermoregulation simulation combined with the proposed local clothing insulation estimation methods. The Jaccard Similarity Coefficient (JSC) increased by an average of 0.21, with body segments like the head, neck, shoulders, back, and arms showing nearly 0.4 or more improvement. These local insulation determination functions, used with a multi-nodal thermoregulation model, offer a simpler and more effective way to enhance thermal comfort assessment accuracy. By providing more precise local insulation values, these functions can help optimize building designs and urban planning strategies, leading to better thermal comfort for occupants.

Molecular characterization and transformation of dissolved organic matter in snow and meltwater from Baishui Glacier No. 1, Mt. Yulong - Lin Feng; Yanmei Liu; Hewen Niu; Jianzhong Xu (Journal of Mountain Science, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Effect of electron beam irradiation on the quality of chicken during post-mortem ageing - Xin Wang; Linya Wang; Jiangtao Yu; Yifeng Teng; Xiaomei Xiang; Dan Zhang; Luyao Kang; Yabin Niu; Xianchao Feng; Lin Chen (Food Chemistry, 2025)

Enhancement of methane production from pig manure by ferrate pretreated anaerobic digestion: Performance and mechanism - Yukai Zheng; Jiarui Wang; Xiaojun Niu; Xintai Su; Xiaoyan He; Yunxia Hu; Dongmei Zhao; Deye Chen; Yu Lin; Kai Li (Chemical Engineering Journal, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

The CG MPNs@UFB composite coatings integrating antibacterial with interface anchoring for sustained protection on inanimate surfaces - Yongxin Zheng; Xi Zhou; Rui Li; Xuejiao Wang; Yabin Niu; Lin Chen; Xianchao Feng (Chemical Engineering Journal, 2025)

Recent advances in 3D cell culture models in cancer drug development - Yae Sol Cha; Alvin Michaels; Janney Z. Wang; Yihe Niu; Yipeng Lin; Ling Zhu; Xue Zhu; Ke Wang; Michael Murray; Fanfan Zhou (Journal of Pharmaceutical Investigation, 2025)
Background In vitro cell culture models are widely used in cancer drug development. However, traditional two-dimensional (2D) models do not replicate the complex characteristics of the tumour microenvironment. Three-dimensional (3D) culture models have been used to prepare cell spheroids that are increasingly used in drug screening and evaluation due to their greater capacity to mimic tumour properties. Area covered This review discusses the methods used to generate 3D cell systems and their applications in cancer research. There are several methods used in the generation of 3D culture models, including forced floating and matrix-based methods. However, bioprinting technologies have emerged more recently as novel approaches to generate 3D culture models that can better mimic tumour physiology. 3D models are used to evaluate the activities of drugs in a wide variety of cancer types, although they have not yet been widely applied in the case of rarer cancers. Expert opinion 3D culture models have a number of desirable features that are advantageous in anti-cancer drug development. However, some methods of spheroid production have issues of inherent non-reproducibility and inconsistency, while bioprinting technology generally has more favourable features. Thus, newer optimised technologies will improve the physiochemical properties of spheroids, which may promote their application in cancer drug development.

Rodent Bioturbation Significantly Enhances Annual Methane Uptake by Tibetan Alpine Grasslands - Dezhao Gan; Dongsheng Yu; Hongchao Zuo; Zheng Li; Zelong Zhang; Huinan Li; Zhenrong Lin; Hui Wang; Qingping Zhou; Jinsong Wang; Shuli Niu; Ruijun Long; et al. (Global Change Biology, 2025)
Tibetan alpine grasslands (AG) serve as critical methane (CH 4 ) sinks, yet face degradation from anthropogenic and climatic disturbances that promote subterranean rodents (e.g., Plateau zokor [ Myospalax baileyi ] and pika [ Ochotona curzoniae ]) activities. Although rodent bioturbation (e.g., burrowing, foraging and excreting) alters soil structure, soil physico‐chemical properties and productivity from AG, its impacts on CH 4 uptake remain poorly understood. Among the first, we combined paired year‐round CH 4 flux measurements from Plateau zokor mounds (ZM) and surrounding healthy meadow (HM) patches in Tibetan alpine meadow with collated CH 4 fluxes from meta‐ and synthetic analyses across Tibetan AG, temperate grasslands (TG) and tropical grasslands (TrG) globally. We observed that rodent bioturbation significantly ( p 4 uptake (HM: −0.91 ± 0.08 kg C ha −1 vs. ZM: −1.80 ± 0.19 kg C ha −1 , mean ± standard error, negative values indicate uptake). Notably, 67% of this net increase (−0.89 ± 0.10 kg C ha −1 year −1 ) due to rodent bioturbation occurred during the growing season. Meta‐analysis results revealed this phenomenon associated with significantly ( p pmoA for methanotrophs. Non‐growing season (NGS) CH 4 uptake contributed 45% and 39% to annual CH 4 uptake for HM and ZM, respectively, falling into the ranges of 12%–64% NGS CH 4 uptake contributions from TG to AG of China. The TrG showed significant ( p 4 uptake than TG and AG globally, due to the fact that significant ( p 4 flux changes and highlight soil moisture as a key driver for global CH 4 sink variations. These results emphasise the need for long‐term monitoring to better assess the ecological consequences of bioturbation in climate‐sensitive alpine ecosystems.

Development of chemiluminescent enzyme immunoassay for the detection of aristolochic acid I in patent medicines and cosmetics - Long Xu; Yuzhu Xu; Yiwen Lin; Jingdi Niu; Xinxing Gao; Wanwan Wang; Shanqin Qian (Toxicon, 2025)

Identifying thresholds of landscape indicators in suitable green space buffer zones based on thermal sensation categories during summer: Empirical study in Chongqing, China - Jiaqi Niu; Hanyu Wang; Hao Guo; Hongqiao Qin; Jie Yan; Lin Ye; Zhiyong Liu; Guifeng Han (Sustainable Cities and Society, 2025)

Extreme degradation of alpine wet meadow decelerates soil heat transfer by preserving soil organic matter on the Qinghai–Tibet Plateau - Zeyong Gao; Chengming Zhang; Wengyan Liu; Fujun Niu; Yibo Wang; Zhanju Lin; Guoan Yin; Zekun Ding; Yunhu Shang; Jing Luo (Journal of Hydrology, 2025)

Insight into carbonyl source based on improved source apportionment method: Alkene regulate secondary formation - Yulong Yan; Yueyuan Niu; Xiaolin Duan; Ke Yue; Jiaqi Dong; Chao Yang; Dongmei Hu; Yuhang Wang; Junjie Li; Lin Peng (Journal of Hazardous Materials, 2025)

Muti-network active aerogel based on PVA, bacterial cellulose, and sodium alginate: Characterization, kinetics studies, and application for mutton preservation - Xi Zhou; Fangqu Wang; Yang Yu; Ruirui Guo; Xinran You; Xiaomei Xiang; Xiaojing Fan; Yabin Niu; Xuejiao Wang; Xianchao Feng; Lin Chen (Food Hydrocolloids, 2025)

Tree-ring dating of the construction of the Yinshan tomb in Shaoxing, Zhejiang Province: A preliminary study - Shiyuan Shi; Congcong Xiao; Zebin Li; Yongxiang Wang; Hui Wang; Zhansheng Niu; Hongyan Zhang; Pengyu Lin; Xinrui Liu; Lingling Lu; Jiangfeng Shi; Huayu Lu (Science China Earth Sciences, 2025)

SlRGLG2-SlBEL2 module regulates drought tolerance in tomato - Xiao-Lin Niu; Gang-Shuai Liu; Xiaodan Zhao; Da-Qi Fu (Plant Molecular Biology, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Unraveling the molecular transformation of textile-dyeing wastewater DOM: A key to optimizing full-scale TDWW treatment performance - Minru Liu; Xiaojun Niu; Zhenrong Lin; Xuechang Ren; Kejing Fang; Zhihua Tang; Qizhe Fan; Kai Li (Journal of Water Process Engineering, 2025)

Volatile organic compounds emission characteristics and factors from stage-dependent combustion in typical biomass stoves in northern China: Field measurements and environmental implications - Ke Yue; Yulong Yan; Zhen Li; Yueyuan Niu; Jiaqi Dong; Yongqian Zhou; Junjie Li; Lin Peng (Environmental Pollution, 2025)

In search of nanofiltration membranes for efficient lithium extraction from carbonate-type salt lakes - Ren-Jie Fan; Chun-Xu Zhang; Fujun Xiong; Lin-Hui Niu; Xiang-Xuan Ruan; Xiaohu Wang; Zhen-Yuan Wang; Mei-Ling Liu; Shi-Peng Sun; Weihong Xing (Desalination, 2025)

Skin-printable, anti-freezing, and recyclable ionic hydrogel bioelectrode for continuous electrophysiological monitoring - Meiqiong Zheng; Leqi Li; Xinyuan Ye; Zichong Ji; Yuli Wang; Zonglei Wang; Shihong Lin; Mingzhe Wang; Wenqing Yan; Jiawei Yang; Pengcheng Zhou; Yujie Zhang; et al. (Chemical Engineering Journal, 2025)

Triethoxysilane-enhanced graphene/carbon nanoparticles conductive network for multifunctional fabric electronics with pressure, temperature and strain sensing capabilities - Yunong Zhao; Jianhong Hao; Zihan Lin; Shaowen Mou; Shujing Feng; Fan Yao; Ziyuan Zhou; Zhitong Wang; Zhaobin Li; Xianghui Li; Xiaowen Zhu; Tianxu Zhang; et al. (Chemical Engineering Journal, 2025)

A significant reduction in the coal contribution to PM2.5 and exposed health risks due to the energy structure transition - Dongmei Hu; Mingyang Yuan; Yulong Yan; Xiaolin Duan; Yafei Guo; Yueyuan Niu; Wen Yan; Lin Peng (Atmospheric Pollution Research, 2025)

Dark nectar pouches are visually similar to colored nectar in bird‐pollinated flowers - Yang Niu; Lie‐Wen Lin; Yi‐Feng Liu; Li‐Shen Qian; Zhe Chen; Hang Sun (Ecology, 2025)

Ferrihydrite enhance performance in anaerobic digestion of pig manure: Methane production, Feammox and metabolic pathway - Yukai Zheng; Jiarui Wang; Xiaojun Niu; Xintai Su; Xiaoyan He; Yunxia Hu; Dongmei Zhao; Deye Chen; Yu Lin; Kai Li (Journal of Water Process Engineering, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Rapid electrothermal upcycling hexachlorobutadiene (HCBD) polluted distillation residue into turbostratic graphene for enhanced electromagnetic wave absorption - Tong Chen; Yunxiao Zhao; Hanyang Sun; Xinyu Niu; Pei Li; Yan Xia; Xiaoqing Lin; Xiaodong Li; Ying Wang; Jianhua Yan; Chen Sun (Journal of Hazardous Materials, 2025)

Degradation of phoxim by ultrasonic assisted calcium sulfite activated persulfate: Kinetics and mechanisms insights - Zhenjun Xiao; Junlong Zhang; Yijie Lin; Kaixuan Zheng; Zili Lin; Mengyang Niu; Wanlin Lin; Yuchun Hong; Zhongyang Li; Ping Chen; Qingbin Song; Wenying Lv; et al. (Journal of Environmental Chemical Engineering, 2025)

Two-stage inoculation with lignocellulose-degrading microorganisms in composting: Enhanced humification efficiency and underlying mechanisms - Yu Zhang; Binfeng Lin; Yuhao Hao; Mengling Lu; De Ding; Shiyuan Niu; Hongquan Xiang; Zhi Huang; Jianbin Li (Environmental Research, 2025)

17β-estradiol inhibits lipopolysaccharide-induced inflammation and pyroptosis of Leydig cells of the domestic yak (Bos grunniens) via the SIRT1/Nox4/ROS pathway - Junyuan Ma; Yanmei Yang; Lin He; Chongfa Yang; Yahua Yang; Yang Li; Wen He; Xiaoying Niu; Zhou Chen; Songming Hu; Jin'e Wang; Yingpai Zhaxi; et al. (Domestic Animal Endocrinology, 2025)

A haplotype-resolved genome assembly of tetraploid Medicago sativa ssp. falcata - Wanying Li; Xuanzhao Li; Wei Li; Haibo Yang; Diandian Guo; Ting Guo; Yingying Meng; Qiang He; Hao Lin; Huilong Du; Lifang Niu (Science China Life Sciences, 2025)

Impact of Energy Transition on CO2 Emissions in China’s Cities - Niu Dang; Qiang Wang; Mei-po Kwan; Jian Lin (Chinese Geographical Science, 2025)

A compact spectroscopic analyzer for simultaneous measurement of N2O, CH4, and CO2 fluxes from soils - Zetong Niu; Longfei Yu; Zhimei Liu; Lifang Wu; Dingxi Chen; Xiaoqing Cui; Tingjung Lin; Yin Wang (Agricultural and Forest Meteorology, 2025)

Frost heave evaluation and prediction of high-speed railway subgrade with coarse filler in high altitude seasonal frozen region, northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Xingwen Fan; Minghao Liu; Chunqing Li; Yunhu Shang (Transportation Geotechnics, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Cardiotoxicity of tris(2-chloroethyl) phosphate exposure: Insights into the role of oxygen sensor mediated energy metabolism remodeling - Ze Zhang; Chuer Zheng; Xinya Gu; Rifat Zubair Ahmed; Hao Yin; Jingxu Zhang; Yongfeng Lin; Jiao Luo; Yong Niu; Xiaoting Jin; Yuxin Zheng (Journal of Hazardous Materials, 2025)

Performances and mechanisms of catalytic ozonation for paint wastewater via catalysts of Fe-Mn deposited within graphitized beads of γ-Al2O3 - Mei Dai; Chunping Yang; Liusiyu Yang; Yan Lin; Shanying He; Xiang Li; Qiuya Niu; Shaohua Wu (Journal of Cleaner Production, 2025)

The mechanism of egg white protein to enhance the thermal gel properties of giant squid (Dosidicus gigas) surimi - Fuge Niu; Xiang Li; Chenyang Lin; Xinyu Hu; Bin Zhang; Weichun Pan (Food Chemistry, 2025)

Insights into nitrogen metabolism and humification process in aerobic composting facilitated by microbial inoculation - Binfeng Lin; Yu Zhang; Yuhao Hao; Mengling Lu; Hongquan Xiang; De Ding; Shiyuan Niu; Kai Li; Jianbin Li; Zhi Huang (Environmental Research, 2025)

Preparation of nitrogen-doped biocarbon from sewage sludge and pine sawdust for superior hydrogen sulfide removal: Experimental and DFT studies - Kai Li; Xiaojun Niu; Lingling Zhou; Yukai Zheng; Zhenrong Lin; Minru Liu (Environmental Research, 2025)

The polarization loss induced by interfacial charge redistribution using Ar plasma treatment in Ni@C composites for superior microwave absorption performance - Jinming Zhang; Mang Niu; Zhaozuo Zhang; Lin Chen; Ruoxin Sun; Zaihao Zhang; Xiaoxia Wang (Chemical Engineering Journal, 2025)

Dimerized small-molecule acceptors with electron withdrawing linker for efficient organic solar cells - Jianan Niu; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Shuguang Wen; Cheng Sun; Mingliang Sun; Xichang Bao (Chemical Engineering Journal, 2025)

Rational design of a starch/whey protein isolate/caffeic acid ternary system to alleviate gel deterioration during freeze-thaw cycles - Qian Lin; Wei Liang; Wenqing Zhao; Li Niu; Wenhao Li (Carbohydrate Polymers, 2025)

Natural starches suitable for 3D printing: Rhizome and seed starch from Millettia speciosa champ, a non-conventional source - Yuanyuan Yan; Zhi Huang; Zhu Zhu; Fengwei Xie; Tao Yang; Lin Zeng; Zhiyao Jiang; Jin Du; Ying Chen; Debao Niu (Carbohydrate Polymers, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Determining the key meteorological factors affecting atmospheric CO2 and CH4 using machine learning algorithms at a suburban site in China - Wanyu Liu; Zhenchuan Niu; Xue Feng; Weijian Zhou; Dan Liang; Guowei Wang; Lin Liu (Urban Climate, 2025)

AFB1 consolidates HBV harm to induce liver injury and carcinogenic risk by inactivating FTCD-AS1-PXR-MASP1 axis - Yaqi Xing; Wusheng Zhong; Xuejun Wu; Zhengzhong Ni; Wenya Lv; Ying Fan; Ling Chen; Haorui Lin; Yangmin Xie; Jianwei Lin; Yongdong Niu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The improved gel properties of myofibrillar protein under low salt condition by ultrasound-assisted sodium tripolyphosphate - Rui Li; Xiaoqi Li; Chen Wang; Guiming Zhang; Yabin Niu; Fashan Wei; Lin Chen; Xianchao Feng (Meat Science, 2025)

Inheritance of Cry2Ab2 resistance in two Helicoverpa zea (Lepidoptera: Noctuidae) populations resistant to single- and dual-Bacillus thuringiensis proteins - Fangneng Huang; Wenbo Yu; Graham P. Head; Ying Niu; Caroline Sakuno; Shucong Lin; Tiago Silva; Bhavana Patla (Journal of Invertebrate Pathology, 2025)

Comparison of vehicular emissions at different altitudes: Characteristics and policy implications - Zhiwen Jiang; Haomiao Niu; Zhenyu Jia; Lin Wu; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Environmental Pollution, 2025)

Enrichment of nanocavities in hollow sandwich catalysts for boosting hydrodeoxygenation of biomass-derived vanillin - Kun Wang; Tian Lin; Gang Zhao; Liang Zhang; Ziqiang Niu; Shuli Yin; Yinglong Wang; Fengbin Zheng (Chemical Engineering Journal, 2025)

Inhibition of odor generation during the composting process of fecal sludge from rural toilets by decomposed compost backfilling - Lin Lin; Xingfeng Yang; Yilin Shen; Ping Zhu; Shiyu Niu; Shakib Alghashm; Guoji Ding; Deli Wu; Xiaowei Li (Bioresource Technology Reports, 2025)

Comparative Analysis of Growth Dynamics and Relative Abundances of Gut Microbiota Influenced by Ketogenic Diet - Mi Tang; Zhidong Zhang; Liyuan Lin; Junling Niu; Guangxun Meng; Wei Wang; Jiwen Wang; Yingyan Wang (Phenomics, 2025)

The evolution and morphodynamic characteristics of shoals and troughs in Lingdingyang Bay of the Pearl River Estuary - Linxi Fu; Yuhang Zhong; Ping Zhang; Lixia Niu; Xiaohe Zhang; Jianliang Lin; Huayang Cai; Qingshu Yang (Frontiers in Marine Science, 2025)
Shoals and troughs are the fundamental geomorphological units of estuarine systems. However, their definition and morphodynamic characteristics, influenced by the complex dynamic environment, remain a critical challenge. This work introduces a depth–area spatial function as a quantitative criterion for the definition of shoals and troughs, while simultaneously elucidating their geodynamic implications. The Lingdingyang Bay (LDB) of the Pearl River Estuary serves as a case study. From 1901 to 2018, the LDB consisted of the West Shoal, Middle Shoal, and East Shoal and the West Trough and East Trough. The threshold depth of the LDB shifted from −5.75 m in 1901 to −4.75 m between 1964 and 2018. The depth–area distribution curve of the LDB exhibits two dominant peak depths (approximately 0 m and −2 m) within the shoal stable state, which categorizes shallow areas into high, medium and low tidal flats. The shoal–trough area ratio in the LDB, relative to the threshold depths, increased from 1901 to 1998, followed by a decline between 2008 and 2018, and culminated in a restoration to the level seen in 1901 (65% shoals and 35% troughs). Regional variations in dominant forces influencing shoal formation and evolution were observed by the vertical classification of the shoal state. The West Shoal is river dominated, the East Shoal is tide dominated, and the Middle Shoal reflects an interaction between riverine inflows and tides. Stabilized curves observed between 2008 and 2018 indicate that this estuary is progressively achieving new equilibrium states. The depth–area spatial function is useful for identifying shoals and troughs within various estuaries, which also provides a geomorphological framework for understanding the estuarine evolution and sediment dynamics.

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

Dietary supplementation of Roseovarius litoreus improves survival and immune defense of the swimming crab Portunus trituberculatus - Mingming Niu; Weichuan Lin; Qingyang Wu; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Astaxanthin regulates high-carbohydrate diet-induced oxidative stress, inflammation and apoptosis in an organ-specific manner in largemouth bass (Micropterus salmoides) - Xuanshu He; Baoyang Chen; Yongkang Chen; Anqi Chen; Sihan Lin; Yucai Guo; Zhihong Liao; Xin Cui; Jin Niu (Aquaculture, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Self-driven electrochemical system for struvite and energy recovery from digested wastewater: Device optimization strategy and long-term operation - Yi-fan Niu; Ting-ting Dong; Zhi-guo Zhao; Meng-Yu Liu; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2025)

Impacts of climate change risk and economic policy uncertainty on carbon prices: Configuration analysis from a complex system perspective - Xing Zhou; Siqing Xing; Jianze Xu; Jiaqi Tian; Anyi Niu; Chuxia Lin (Journal of Environmental Management, 2025)

Formation mechanism of giant squid myofibrillar protein aggregates induced by egg white protein during heat treatment - Fuge Niu; Chenyang Lin; Huabin Liao; Bin Zhang; Jian Zhang; Weichun Pan (Food Hydrocolloids, 2025)

Cleanformer: A Confident Learning Based ERP Label Denoising Framework for Public Attitude Assessment to Recycled Water - Yong Peng; Shuxiang Lin; Jiachen Niu; Hanliang Fu; Chaojie Fan (Water Resources Management, 2025)

Protein Phosphatase 2ACα Regulates ATR-Mediated Endogenous DNA Damage Response Against Microcephaly - Lin Lin; Jing Ding; Simeng Liu; Chunying Liu; Qing Li; Xiang Gao; Yamei Niu; Wei-Min Tong (Molecular Neurobiology, 2025)

Multi-Temporal Energy Management Strategy for Fuel Cell Ships Considering Power Source Lifespan Decay Synergy - Xingwei Zhou; Xiangguo Yang; Mengni Zhou; Lin Liu; Song Niu; Chaobin Zhou; Yufan Wang (Journal of Marine Science and Engineering, 2024)
With increasingly stringent maritime environmental regulations, hybrid fuel cell ships have garnered significant attention due to their advantages in low emissions and high efficiency. However, challenges related to the coordinated control of multi-energy systems and fuel cell degradation remain significant barriers to their practical implementation. This paper proposes an innovative multi-timescale energy management strategy that focuses on optimizing the lifespan decay synergy of fuel cells and lithium batteries. The study designs an attention-based CNN-LSTM hybrid model for power prediction and constructs a two-stage optimization framework: The first stage employs Model Predictive Control (MPC) for long-term power planning to optimize equivalent hydrogen consumption, while the second stage focuses on real-time power allocation considering both power source degradation and system operational efficiency. The simulation results demonstrate that compared to single-layer MPC and the Equivalent Consumption Minimization Strategy (ECMS), the proposed method exhibits significant advantages in reducing single-voyage costs, minimizing differences in power source degradation rates, and alleviating power source stress. The overall performance of this strategy approaches the global optimal solution obtained through Dynamic Programming, comprehensively validating its superiority in simultaneously optimizing system economics and durability.

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Quaternary provenance changes in the loess deposits of the western Chinese Loess Plateau: Insights from U-Pb age spectra of detrital zircon - Yanning Niu; Lin Qi; Yansong Qiao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Aerobic or anaerobic? Microbial degradation of per- and polyfluoroalkyl substances: A review - Qiuqi Niu; Xinrong Lin; Xiong Zheng; Yang Wu; Min Long; Yinguang Chen (Journal of Hazardous Materials, 2024)

Insights into novel phosphorus-doped biochar for tetracycline removal: Non-radical oxidation and adsorption - Xi Fu; Xiaojun Niu; Dongqing Zhang; Ling Li; Xingyao Ye; Shan Liao; Maoyu Li; Chuting Lao; Deye Chen; Yu Lin; Zhiquan Yang (Journal of Environmental Chemical Engineering, 2024)

Inventory of active rock glaciers and their distribution characteristics on the Qinghai-Tibet Plateau and its adjacent mountainous regions - Nuocheng Li; Zhanju Lin; Huini Wang; Fujun Niu; Xingwen Fan; Jing Luo; Wenjiao Li; Xuyang Wu (Geomorphology, 2024)

Subjective information in thermal comfort evaluation methods: A critical review - Yuxin Yang; Junmeng Lyu; Zhiwei Lian; Yongxin Xie; Ying Jiang; Junwei Lin; Jianlei Niu (Energy and Buildings, 2024)

Photo-transformation of biochar-derived dissolved organic matter and its binding with phenanthrene/9-phenanthrol: The role of functional group and pyrolysis temperature - Yifan Niu; Siyao Wang; Peng Gao; Xin Ren; Fangfang Li; Zhanpeng Liu; Lin Wang; Hongbo Peng; Shaohua Ju (Bioresource Technology, 2024)

Evaluating thermal sensation in outdoor environments - Different methods of coupling CFD and radiation modelling with a human body thermoregulation model - Dharmasastha K; Haobin Liang; Junwei Lin; Yongxin Xie; Yichen Yu; Jian-lei Niu (Building and Environment, 2024)

Hydroxyl radicals in ozone-based advanced oxidation of organic contaminants: A review - Mei Dai; Qiuya Niu; Shaohua Wu; Yan Lin; Jayanta Kumar Biswas; Chunping Yang (Environmental Chemistry Letters, 2024)

PFOS impairs cardiac function and energy metabolism under high-fat diet: Insights into role of circulating macrophage emphasized by exposure distribution - Ze Zhang; Hao Yin; Chuer Zheng; Zhenhua Yu; Rifat Zubair Ahmed; Yong Niu; Chengying Zhou; Jian Ding; Huan Lin; Yongfeng Lin; Yuxin Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

Improved identification and monitoring of meteorological, agricultural, and hydrological droughts using the modified nonstationary drought indices in the Yellow River Basin of China - Ben Niu; Yi Li; De Li Liu; Lulu Xie; Lei Wang; Xiaohui Jiang; Hao Feng; Qiang Yu; Jianqiang He; Haixia Lin (Journal of Hydrology, 2024)

Unlocking the roles of wheat root exudates in regulating laccase-catalyzed estrogen humification - Ziyan Niu; Shenghua Xiao; Guoning Zhou; Kai Sun; Hui Lin; Guodong Fang; Youbin Si (Journal of Hazardous Materials, 2024)

Effect of electron beam pretreated wheat flour on dough properties - Li Niu; Mengting Yan; Wei Liang; Qian Lin; Qi Zhao; Ruijie Li; Xinyu Wang; Raushan Moldakhmetova; Wenhao Li (Journal of Cereal Science, 2024)

Advances in the preparation and application of cyclodextrin derivatives in food and the related fields - Zhiheng Zhang; Jingxian Niu; Jilong Wang; Qiaoxin Zheng; Wenbo Miao; Qianzhu Lin; Xiaojing Li; Zhengyu Jin; Chao Qiu; Shangyuan Sang; Hangyan Ji (Food Research International, 2024)

Targeted quantitative metabolomic and flavor objective quantification technique reveal the impact mechanism of shaking on black tea quality and non-volatile metabolites - Jinjin Wang; Lichi Qu; Ziming Yu; Yongwen Jiang; Chengfa Yu; Xizhe Zhu; Qingju Lin; Linchi Niu; Yaya Yu; Qing Lin; Yan Shang; Haibo Yuan; et al. (Food Chemistry, 2024)

Observations of avalanche–substrate interactions in the Iymek rock avalanche deposit: A possible causative mechanism - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Engineering Geology, 2024)

Heteronuclear FeN3-CuN3 atom pairs coordination engineering of single-atom catalysts for water splitting and Zn-Air batteries - Yinglin Zhang; Bo Yan; Chenchen Ji; Tingting Wei; Wenbin Niu; He Lin; Yulin Shi (Chemical Engineering Journal, 2024)

Recent advances in anti-infective catheters for preventing catheters associated urinary tract infections - Liyuan Liu; Baoxia Xue; Mei Niu; Lin Chen; Yongzhen Yang; Bingshe Xu; Li Zhang (Chemical Engineering Journal, 2024)

Atomically dispersed Fe-N4 sites in activation of peroxymonosulfate for wastewater purification: Mechanism of non-radical pathways and their quantification - Lin Niu; Zhi Tang; Qitao Lei; Yaqi Cai; Junyu Wang; Deyi Hou; Xiaoli Zhao; Fengchang Wu (Chemical Engineering Journal, 2024)

Temporal characteristics and vertical profiles of atmospheric CH4 at the northern foot of the Qinling Mountains in China - Wanyu Liu; Xue Feng; Zhenchuan Niu; Weijian Zhou; Huilin Chen; Dan Liang; Mengni Lyu; Guowei Wang; Lin Liu (Atmospheric Environment, 2024)

HRD1 reduction promotes cholesterol-induced vascular smooth muscle cell phenotypic change via endoplasmic reticulum stress - Linli Wang; Zhitao Ren; Lin Wu; Ximei Zhang; Min Wang; Haiming Niu; Xuemin He; Heting Wang; Yanming Chen; Guojun Shi; Xiaoxian Qian (Molecular and Cellular Biochemistry, 2024)

Navigation spoofing interference detection based on Transformer model - Ben Niu; Xuebin Zhuang; Zijian Lin; Linjie Zhang (Advances in Space Research, 2024)

Optimizing shrimp nutrition and health: ginseng saponins as functional additives in low-fishmeal diets on Litopenaeus vannamei - Sihan Lin; Rong Yao; Xin Cui; Yucai Guo; Denghui Hu; Bin Zhou; Zhaobin Zhou; Xuanshu He; Zhihong Liao; Beiping Tan; Jin Niu (Frontiers in Marine Science, 2024)
The research investigated the nutritional physiology effect of ginseng saponins on Litopenaeus vannamei ( L. vannamei ) under low-fishmeal diets. In total, five experimental groups were arranged, with 21% fishmeal (high-fishmeal) serving as the positive control (PC), 11% fishmeal (low-fishmeal) serving as the negative control (NC), and 11% fishmeal serving as the addition in all three other groups. Similarly, ginseng saponins (GSP, purity of 2%) were added in the order of 0.1%, 0.3%, and 0.5% (GSP0.1, GSP0.3, and GSP0.5), with an 8-week growth cycle. Both GSP0.1 and GSP0.3 showed significantly higher growth performance (final body weight, FBW; weight gain rate, WGR; specific growth rate, SGR) than the NC group, but significantly lower growth performance than the PC group ( P <0.05). However, it was found that there was no significant difference in the body composition of the whole shrimp between the experimental groups. Compared to the PC group, the GSP0.3 group exhibited significantly elevated levels of antioxidant enzymes, total antioxidant capacities (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) ( P <0.05). Additionally, significant differences were observed between the PC and GSP0.3 groups regarding the expression levels of sod , cat , and gsh-px (P<0.05). And there was a better morphological organization of shrimp hepatopancreas in the GSP0.3 group than in all other groups. In comparison with the PC group, there was no significant difference in shrimp survival rates after ammonia nitrogen stress with ginseng saponins added ( P >0.05). Whereas, in terms of the relative expression levels of the corresponding genes, in shrimp of the GSP0.3 group, the relative expression of antioxidant-related genes sod , cat , and gsh-px were significantly higher than that of the PC group ( P <0.05). Caspase3 and p53 , along with bcl-2 and bax , were found to be significantly more expressed in shrimp of the GSP0.3 group than in all other groups ( P <0.05). These findings imply that in addition to improving growth performance, adding ginseng saponins at a concentration of 11% fishmeal could improve the antioxidant capacity of L. vannamei as well as its resistance to stress. Therefore, ginseng saponins can be utilized as a functional additive to increase L. vannamei growth performance, enhance antioxidant capacity, and reduce stress in low-fishmeal diets, 0.3% of ginseng saponins is optimal.

An extended investigation on allele frequency of resistance to Bt maize in the southwestern corn borer and sugarcane borer (Lepidoptera: Crambidae) in the mid-south region of the United States - Fangneng Huang; Ying Niu; Qisheng Song; Scott Stewart; Blake Wilson; Graham Head; Sebe Brown; Wenbo Yu; Tiago Silva; Caroline Sakuno; Shucong Lin (Crop Protection, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Evidence for sustainably reducing secondary pollutants in a typical industrial city in China: Co-benefit from controlling sources with high reduction potential beyond industrial process - Yueyuan Niu; Yulong Yan; Jiaqi Dong; Ke Yue; Xiaolin Duan; Dongmei Hu; Junjie Li; Lin Peng (Journal of Hazardous Materials, 2024)

Enhanced B-type starch granules proportion modulates starch-gluten interactions during the thermal processing of reconstituted doughs - Qian Lin; Wei Liang; Huishan Shen; Li Niu; Wenqing Zhao; Wenhao Li (Food Chemistry, 2024)

A naturaly attenuated largemouth bass ranavirus strain provided protection for Micropterus salmoides by immersion immunization - Xiaozhe Fu; Wenxian Li; Cong Liu; Xia Luo; Qiang Lin; Yinjie Niu; Hongru Liang; Baofu Ma; Ningqiu Li (Fish & Shellfish Immunology, 2024)

The GLCCI1/STAT3 pathway: a novel pathway involved in diabetic cognitive dysfunction and the therapeutic effect of salidroside - Lin Niu; Min Xu; Wenqiang Liu; Hongdan Yu; Shengxue Yu; Fuzhi Li; Teng Wang; Die Sun; Tiefeng Yao; Wanze Li; Zhengzhong Yang; Xuezheng Liu; et al. (Journal of Molecular Histology, 2024)

A 3D bedrock modeling method based on information mining of 2D geological map - Tong Niu; Bingxian Lin; Liangchen Zhou; Guonian Lv (Earth Science Informatics, 2024)

Cumulative frost heave and hydrothermal process of the high-speed railway subgrade under extreme climate conditions in northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Yunhu Shang; Xingwen Fan (Transportation Geotechnics, 2024)

Greenhouse gas emissions and carbon and water footprints during processing of Lei bamboo shoots - Zixiang Weng; Shuiqin Lu; Xuekun Cheng; Chunyu Pan; Guangyu Wang; Dejin Dong; Zhengcai Li; Ziliang Zhao; Lei Gu; Linghui Dong; Zhengwen Niu; Chong Li; et al. (Journal of Cleaner Production, 2024)

Pickering emulsions stabilized by essential oil-tannin-chitosan particles: Microstructure, stability, antibacterial activity, and antioxidant activity - Jingxian Niu; Qianzhu Lin; Xiaojing Li; David Julian McClements; Hangyan Ji; Zhengyu Jin; Chao Qiu (Food Hydrocolloids, 2024)

A comprehensive evaluation framework for building energy systems considering economic efficiency, independence, and building–grid interaction performance indicators - Lu Yue; Jide Niu; Zhe Tian; Quanyi Lin; Yakai Lu (Energy and Buildings, 2024)

Biomimetic cellulose membrane enables high-performance salinity gradient energy conversion: Coupling surface charge and nanopore structure - Jianping Shi; Kairui Lin; Yuanyuan Liu; Shengyue Niu; Yu Zhang; Weikai Yang; Liulian Huang; Jianguo Li; Lihui Chen (Chemical Engineering Journal, 2024)

Intermittent demand-controlled ventilation for energy flexibility and indoor air quality - Dun Niu; Yuxin Li; Sheng Zhang; Zhang Lin (Building and Environment, 2024)

PRC2 primes bivalent genes for transcription induction independent of histone methyltransferase activity - Meihan Gong; Ye Yuan; Zhongye Dai; Xuejiao Lv; Jiacheng Su; Dawei Huo; Lin Niu; Xu Chen; Xudong Wu (Science China Life Sciences, 2024)

Down-regulation of RTEL1 Improves M1/M2 Macrophage Polarization by Promoting SFRP2 in Fibroblasts-derived Exosomes to Alleviate COPD - He-Ping Xu; Feng Zhan; Hong Wang; Jie Lin; Huan Niu (Cell Biochemistry and Biophysics, 2024)

Observed surface heat fluxes partitioning during the local growing season over the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Danrui Sheng; Hanlin Niu; Peili Wu; Zhaoguo Li; Lin Zhao; Hao Chen; Lunyu Shang; Shaoying Wang; Shihua Lyu (Agricultural and Forest Meteorology, 2024)

Spatiotemporal Variability and Environmental Controls of Temperature Sensitivity of Ecosystem Respiration across the Tibetan Plateau - Danrui Sheng; Xianhong Meng; Shaoying Wang; Zhaoguo Li; Lunyu Shang; Hao Chen; Lin Zhao; Mingshan Deng; Hanlin Niu; Pengfei Xu; Xiaohu Wen (Advances in Atmospheric Sciences, 2024)

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

A systematic review on percarbonate-based advanced oxidation processes in wastewater remediation: From theoretical understandings to practical applications - Ling Li; Xiaojun Niu; Dongqing Zhang; Xinyao Ye; Zhilin Zhang; Qiang Liu; Lei Ding; Kun Chen; Yang Chen; Kunyang Chen; Zhaocai Shi; Zhang Lin (Water Research, 2024)

In situ N-doping engineered biochar catalysts for oxidation degradation of sulfadiazine via nonradical pathways: Singlet oxygen and electron transfer - Lin Niu; Qitao Lei; Tianhui Zhao; Zhi Tang; Yaqi Cai; Deyi Hou; Siyuan Zhang; Mengyuan Fang; Guoqing Hou; Xiaoli Zhao; Fengchang Wu (Science of The Total Environment, 2024)

Soil organic matter components and sesquioxides integrally regulate aggregate stability and size distribution under erosion and deposition conditions in southern China - Geng Guo; Yu Kong; Yanyin Xu; Xiaoying Peng; Manting Niu; Guangruo Zeng; Zhen Ouyang; Jun Liu; Chen Zhang; Jie Lin (Journal of Hydrology, 2024)

A novel red-to-near-infrared AIE fluorescent probe for detection of Hg2+ with large Stokes shift in plant and living cells - Haiyi Niu; Tianqing Ye; Liangyi Yao; Yanfei Lin; Kan Chen; Yanbo Zeng; Lei Li; Longhua Guo; Jianbo Wang (Journal of Hazardous Materials, 2024)

Visible light-driven characterisation of AgI/CeO2/rGO nanocomposites and their application in levofloxacin degradation - Zhixin Ren; Lin Yang; Xiaoxue Tang; Qing Xu; Yanan Niu; Yuguang Lv; Mingyuan Liu (Journal of Environmental Chemical Engineering, 2024)

The Meso-Tethys Ocean: The nature, extension and spatial-temporal evolution - Jian-Jun Fan; Bo-Chuan Zhang; Jian-Bo Zhou; Yaoling Niu; Si-Lin Sun; Jun-Pu Lv; Yang Wang; Yu-Jie Hao (Earth-Science Reviews, 2024)

Recent rapid initiation and growth of retrogressive thaw slumps in the Hoh Xil region of the Qinghai-Tibetan Plateau - Jing Luo; Fan Yu; Fujun Niu; Miaomiao Yao; Zhanju Lin; Minghao Liu; Guoan Yin; Zeyong Gao (CATENA, 2024)

A medium to long-term variations in hydrothermal process and deformation of high-speed railway subgrade in high-altitude cold region, Northwest China - Xuyang Wu; Zhanju Lin; Fujun Niu; Yunhu Shang; Chunqing Li (Cold Regions Science and Technology, 2024)

Daphmacrimines A−K, Daphniphyllum alkaloids from Daphniphyllum macropodum Miq - Li-Li Xu; Zhen-Peng Niu; Duo-Zhi Chen; Yu Zhang; Qian Zhao; Hong Liang; Sheng Li; Jin-Liang Li; Xiao Ding; Chong-Lin Yang; Xiao-Jiang Hao (Phytochemistry, 2024)

Machine learning-enabled high-throughput industry screening of edible oils - Peishan Deng; Xiaomin Lin; Zifan Yu; Yuanding Huang; Shijin Yuan; Xin Jiang; Meng Niu; Weng Kung Peng (Food Chemistry, 2024)

A stable colorimetric biosensor for highly selective detection of malathion residue in food based on aptamer-regulated laccase-mimic activity - Linghui Huang; Yue Tang; Jianxun Han; Xiaojuan Niu; Xin Lin; Yuangen Wu (Food Chemistry, 2024)

Global climate change: Effects of future temperatures on emergency department visits for mental disorders in Beijing, China - Yan-Lin Niu; Feng Lu; Xue-Jiao Liu; Jun Wang; De Li Liu; Qi-Yong Liu; Jun Yang (Environmental Research, 2024)

Grey-box modeling for thermal dynamics of buildings under the presence of unmeasured internal heat gains - Xinyi Lin; Zhe Tian; Wenjie Song; Yakai Lu; Jide Niu; Qiang Sun; Yanan Wang (Energy and Buildings, 2024)

Building extra transport channels in mixed-matrix membrane for air dehumidification - Yingtian Xu; Junwei Xie; Runfeng Lin; Yuqi Zhu; Jiayi Wu; Rujing Hou; Runping Niu; Yichang Pan (Journal of Environmental Chemical Engineering, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

Tissue factor pathway inhibitors disrupt structures of rhabdovirus/ranairidovirus and inhibit viral infection in Chinese perch, Siniperca chuatsi - Baofu Ma; Jingkang Li; Min Zhang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Xia Luo; Lihui Liu; Jianguo Su; Jin Zhou; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Self-adaptive and soft-contact ellipsoidal pendulum-structured triboelectric nanogenerator for harvesting water wave energy - Bingqi Zhao; Yong Long; Tianci Huang; Jianan Niu; Yuxiu Liu; Wei Sha; Jiangwen Wang; Zhong Lin Wang; Junyi Zhai; Weiguo Hu (Chemical Engineering Journal, 2024)

Engineering of local electron properties optimization in single-atom catalysts enabling sustainable photocatalytic conversion of N2 into NH3 - Tianren Liu; Wensheng Zhang; Qingmei Tan; Weilong Lian; Haiting Lin; Jianshen Li; Dongxue Han; Yingying Fan; Dongdong Qin; Li Niu (Chemical Engineering Journal, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

Characterization of a novel recombinant NADC30‑like porcine reproductive and respiratory syndrome virus in Shanxi Province, China - Jianle Ren; Shanshan Tan; Xinxin Chen; Xizhen Wang; Yiting Lin; Yi Jin; Sheng Niu; Ying Wang; Xiaolong Gao; Libin Liang; Junping Li; Yujun Zhao; et al. (Veterinary Research Communications, 2024)

Expression characteristics and interference analysis of glucose-6-phosphate dehydrogenase reveal its importance in Pyropia yezoensis under salt stress - Li Huan; Mengmeng Shi; Guohong Lin; Baoyu Zhang; Xiujun Xie; Menglin Guo; Xi Qiang; Zhaojia Ge; Jianfeng Niu; Zhenbing Zheng; Xulei Wang; Guangce Wang (Algal Research, 2024)

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

Study on Sensitivity Mechanism of Low-Permeability Sandstone Reservoir in Huilu Area of Pearl River Mouth Basin - Hongbo Li; Lin Ding; Qibiao Zang; Qiongling Wu; Yongkun Ma; Yuchen Wang; Sandong Zhou; Qiaoyun Cheng; Xin Tian; Jiancheng Niu; Mengdi Sun (Journal of Marine Science and Engineering, 2024)
Reservoir sensitivity is a parameter that is used to evaluate the degree of change in reservoir permeability under the influence of external fluids. Accurate evaluation of reservoir sensitivity is conducive to the optimization of fluid parameters during exploration and development. Taking the Wenchang Formation and Enping Formation of the Paleogene in the Huilu area of the Pearl River Mouth Basin as the research object, reservoir sensitivity experiments were carried out. Combined with the corresponding experimental results obtained using methods such as thin section identification, scanning electron microscopy (SEM), X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), and screening analysis, based on mineral sensitization and pore structure sensitization, qualitative and quantitative evaluations of reservoir sensitivity were carried out, and factors affecting sensitivity and sensitization mechanisms were analyzed. This work shows the following: (1) The sandstone reservoirs in the two areas have the same clay type, but the total clay content of the Wenchang Formation is greater than that of the Enping Formation. The porosity of the Wenchang Formation is less developed than the Enping Formation. (2) The Wenchang Formation has weak or moderately weak water sensitivity and moderately weak or moderately strong flow velocity sensitivity. The water sensitivity of the Enping Group samples is moderately weak or moderately strong, the flow rate sensitivity is moderately weak, the alkali sensitivity is weak, the acid sensitivity is moderately weak, and the salinity sensitivity is moderately weak or moderately strong. (3) The sensitivity of the Wenchang Formation is mainly affected by the content of clay minerals. The sensitivity of the Enping Formation is also affected by the clay content and type. Although the clay content is not high, the permeability is more susceptible to sensitivity due to the pore structure and debris particle distribution characteristics. These conclusions are beneficial for the selection of fluid parameters and efficient reservoir development.

Recent advances in swine wastewater treatment technologies for resource recovery: A comprehensive review - Lingling Zhou; Ming Liang; Dongqing Zhang; Xiaojun Niu; Kai Li; Zitao Lin; Xiaojun Luo; Yuying Huang (Science of The Total Environment, 2024)

Manure replacing synthetic fertilizer improves crop yield sustainability and reduces carbon footprint under winter wheat–summer maize cropping system - Jincan Niu; Qudsia Saeed; Wenning Wang; Runze Zhang; Lin Liu; Fenglian Lv; Jiaxing Xu; Yan Han; Panxin Zhang; Changlu Hu; Hu Xu; Benhua Sun; et al. (Journal of Environmental Management, 2024)

Tracking the changes of dissolved organic matter throughout the city water supply system with optical indices - Jinjin Lin; Liyang Yang; Wan-E Zhuang; Yue Wang; Xiaochen Chen; Jia Niu (Journal of Environmental Management, 2024)

Distinctive shear zones demonstrate pervasive laminar cataclastic flow throughout the gigantic Iymek rock avalanche - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Tianhua Li; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Geomorphology, 2024)

Analyzing ozone formation sensitivity in a typical industrial city in China: Implications for effective source control in the chemical transition regime - Yueyuan Niu; Yulong Yan; Yiran Xing; Xiaolin Duan; Ke Yue; Jiaqi Dong; Dongmei Hu; Yuhang Wang; Lin Peng (Science of The Total Environment, 2024)

Atmospheric CO2 and 14CO2 observations at the northern foot of the Qinling Mountains in China: Temporal characteristics and source quantification - Wanyu Liu; Zhenchuan Niu; Xue Feng; Weijian Zhou; Dan Liang; Mengni Lyu; Guowei Wang; Xuefeng Lu; Lin Liu; Jocelyn C. Turnbull (Science of The Total Environment, 2024)

Isolation and characterization of seven neovibsane-type diterpenoids from Viburnum odoratissimum and their neuroblastoma cell protective effects - Jin-Ling Han; Tian-Ming Lv; Jia-Qi Niu; Jin-Le Hao; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Insight into an efficient microalgae co-culture system for biogas slurry treatment: Nutrients recovery and valuable biomass production - Lingling Zhou; Xiaojun Niu; Dongqing Zhang; Chunyang Tao; Yuejin Liu; Kai Li; Lin Zitao; Yongxin Liu; Yu Lin (Journal of Water Process Engineering, 2024)

Transesterification of acidic palm oil using solid waste/CaO as a bifunctional catalyst - Jisen Liu; Tong Lin; Shengli Niu; Jie Zhu; Zihao Yang; Jie Geng; Sitong Liu; Yue Zheng; Bo Liang; Xiaobin Sun; Huaji Zhang (Fuel, 2024)

Colorimetric sensor and visual enzyme sheets for sensitive detection of dimethoate residue in vegetables based on laccase-like activity of coral-like silver citrate - Lian Xia; Jianxun Han; Xiaohuan Huang; Xiaojuan Niu; Xin Lin; Yuangen Wu (Food Control, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

Metal-phenolic nanocatalyst rewires metabolic vulnerability for catalytically amplified ferroptosis - Yang Zhu; Xuegang Niu; Tiantian Wu; Junjie Cheng; Jianhua Zou; Yuanbo Pan; Yu Tian; Wei Huang; Chengyu Ding; Yuanxiang Lin; Dezhi Kang; Xiaoyuan Chen (Chemical Engineering Journal, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Insights into the enhanced mechanism of electron beam pretreatment on application performance for poly (butylene adipate-co-terephthalate)/acetylated cellulose composite plastics - Li Niu; Xinyi He; Xiuyun Zhang; Wei Liang; Qian Lin; Wenhao Li (Carbohydrate Polymers, 2024)

High-Pressure Behavior of Ferromagnesite (Mg0.81Fe0.19)CO3 by Synchrotron X-Ray Diffraction and Raman Spectroscopy up to 53 GPa - Lin Liang; Guibin Zhang; Shengxuan Huang; Jingjing Niu; Dongzhou Zhang; Jingui Xu; Wen Liang; Shan Qin (Journal of Earth Science, 2024)

Changes in Sea Level along the South China Sea Coast Based on the Homogenized Tide Gauge Data - Yan Li; Lin Mu; Dawei You; Jiaying Wang; Qianru Niu; Xiaomei Liao (Journal of Marine Science and Engineering, 2024)
To estimate the changes in the annual mean sea level (MSL) and extreme sea levels (ESLs), the largest collection of tide gauge records from 10 tidal stations along the northern coast of the South China Sea (SCS) were analyzed in this study. Here, all the tide gauge records had been homogenized by a two-step process involving the detection of inhomogeneities, that is, breakpoints caused by non-climatic changes and the application of the adjustment. The study’s conclusions, based on the homogenized tide gauge records, can be summarized as follows: The instrument change and station relocation are the main causes for the identified inhomogeneities. From 1989 to 2018, the sea level along the SCS was at an average rate of 4.0 mm per year, as measured by the homogenized tide gauges. The ESLs from the nine tidal stations rose notably with interannual fluctuations, except for the XSA station. Additionally, the ESLs exhibited substantial decadal variations. The ESLs rose along the northern coast of the SCS and were accelerated at most stations throughout the whole study period, especially after the 1980s. There were significant positive correlations between the ESL and the annual MSL at most tide gauges. The MSL’s changes, especially long-term changes, play an important role in the change in ESLs.

Effect of characteristic parameters of air-bleeding/blowing interface on tunnel pressure waves in streamlined regions of high-speed trains: A numerical simulation study - Kailong Jin; Lin Zhang; Xinzhe Li; Lindong Li; Jiahui Chen; Jinke Wang; Jiqiang Niu (Sustainable Cities and Society, 2024)

Investigating the impact of high-altitude on vehicle carbon emissions: A comprehensive on-road driving study - Zhiwen Jiang; Lin Wu; Haomiao Niu; Zhenyu Jia; Zhaoyu Qi; Yan Liu; Qijun Zhang; Ting Wang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2024)

Transition of organic matter from allochthonous to autochthonous alters benthic nutrient dynamics via microbial food webs - Nan Yang; Yi Li; Li Lin; Lihua Niu; Wenlong Zhang; Longfei Wang (Science of The Total Environment, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Palaeoenvironmental changes in the Late Triassic lacustrine facies of the Ordos Basin of Northwest China were driven by multistage volcanic activity: Implications for the understanding the Carnian Pluvial Event - Miruo Lin; Kelai Xi; Yingchang Cao; Xiaobing Niu; Weijiao Ma; Xiujuan Wang; Shang Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Investigation on the preparation of coal slime flotation microemulsion collector: A combination of experimental and simulation method - Meng He; Jingwei Wang; Jida Niu; Hao Lyu; Liqing Sun; Xiaofang You; Lin Li; Qingbiao Wang (Fuel, 2024)

pH-responsive PVA/konjac glucomannan/functional liposome terpolymer composites: Spotlight on its structure-performance, functionality, barrier properties, controlled-release behavior, biodegradability, and its intelligent preservation role for food - Wei Liang; Xiangzhen Ge; Qian Lin; Li Niu; Wenqing Zhao; Xinyue Liu; Shuangfeng Guo; Marat Muratkhan; Wenhao Li (Food Packaging and Shelf Life, 2024)

Dual-Coordinated atomically dispersed Pt nanozymes evoke efficient pyroptosis for cancer immunotherapy - Jingqi Chen; Yanping Tang; Yan Lin; Xiuxin Lu; Lineng Wei; Shiyu Xia; Wenxin Niu; Weizhong Tang; Weiqing Zhang (Chemical Engineering Journal, 2024)

An eco-friendly versatile superabsorbent hydrogel based on sodium alginate and urea for soil improvement with a synchronous chemical loading strategy - Chenxi Niu; Zhibo Lin; Qian Fu; Yutao Xu; Youhui Chen; Lingbin Lu (Carbohydrate Polymers, 2024)

Short-term exposure to ozone may trigger the onset of Kawasaki disease: An individual-level, case-crossover study in East China - Yixiang Zhu; Renjie Chen; Cong Liu; Yue Niu; Xia Meng; Su Shi; Kexin Yu; Guoying Huang; Liping Xie; Siyuan Lin; Min Huang; Meirong Huang; et al. (Chemosphere, 2024)

Sulfur atom-directed metal–ligand synergistic catalysis in zirconium/hafnium-oxo clusters for highly efficient amine oxidation - Sheng-Nan Sun; Qian Niu; Jiao-Min Lin; Li-Ling He; Jing-Wen Shi; Qing Huang; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Trends in research on characterization, treatment and valorization of hazardous red mud: A systematic review - Anyi Niu; Chuxia Lin (Journal of Environmental Management, 2024)

A digital platform for One-Pot signal enhanced foodborne pathogen detection based on mesophilic argonaute-driven polydisperse microdroplet reactors and machine learning - Junping Wen; Minjie Han; Niu Feng; Guoxun Chen; Feng Jiang; Jianhan Lin; Yiping Chen (Chemical Engineering Journal, 2024)

Mechanism of ferrous ions reversibly inhibiting of oxidase-Like activity of Co3O4 nanowires and its application in horticultural fertilizer analysis - Ziting Lin; Tao Dong; Lingxi Niu; Xin Zhang; Mingyang Wang; Xuan Liu; Yuanyuan Cai; Aihua Liu (Chemical Engineering Journal, 2024)

Modulating surface zinc species via facet engineering for efficient electroreduction of CO2 to CO - Junjie Wang; Zhaozhao Zhu; Yingxi Lin; Xueqiang Qi; Zhao Li; Jinxia Jiang; Xiaobin Niu; Jun Song Chen; Rui Wu (Chemical Engineering Journal, 2024)

Deformation and structure strength anisotropy of undisturbed loess in tunnels on high-speed railway, China - Xuyang Wu; Fujun Niu; Qingguo Liang; Chunqing Li; Zhanju Lin (Transportation Geotechnics, 2024)

Preparation of refined phosphoric acid with recycling of raffinate acid by the extraction of metal impurities - Xiaokang Gong; Chao Hu; Yanru Jin; Haifeng Liu; Jiahui Bai; Lixue Niu; Lin Yang (Journal of Cleaner Production, 2024)

Culex quinquefasciatus membrane-bound alkaline phosphatase is a putative receptor for Lysinibacillus sphaericus Tpp49Aa1 toxin - Qingyun Guo; Wei Li; Yingchao Niu; Xiaohua Dai; Lin Chen (Insect Biochemistry and Molecular Biology, 2024)

The mediating effect of perceived stress on the relationship between big five personality traits and suboptimal health status in Chinese population: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Qihua Guan; Hualei Dong; Zhihui Zhang; Zheng Guo; Zi Lin; Hui Niu; Yibo Wu; Haifeng Hou (EPMA Journal, 2023)

Thermal bleaching in the northern South China Sea: impact of abnormal environment and climate on high-latitude coral reefs - Xin Wang; Yinqiang Li; Mingqing Lin; Zhiwei Che; Weihua Mo; Yanli Chen; Shaohua Mo; Wentao Niu; Haolang Zhou (Environmental Science and Pollution Research, 2023)

In vivo and in vitro, antiviral effects of two mixture of Chinese herbal drug active monomers against MSRV and LMBV in largemouth bass (Micropterus salmoides) - Yinjie Niu; Xiaozhe Fu; Qiang Lin; Hongru Liang; Xia Luo; Shaozhi Zuo; Lihui Liu; Ningqiu Li (Aquaculture, 2023)

Record-breaking marine heatwave in northern Yellow Sea during summer 2018: Characteristics, drivers and ecological impact - Yan Li; Guoyu Ren; Qingyuan Wang; Lin Mu; Qianru Niu; Hanxiang Su (Science of The Total Environment, 2023)

Comparison of microalgae cultivation modes for advanced wastewater purification and pollutant-resource conversion: A pilot study - Lin-Lan Zhuang; Pengfei Yang; Shuang Liang; Tong Yu; Chao Liu; Tingting Zhao; Guoliang Tan; Yueying Niu; Jian Zhang (Journal of Water Process Engineering, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Formation and detection of biocoronas in the food industry and their fate in the human body - Qian Wu; Mengyao Niu; Chen Zhou; Yaxiong Wang; Jianhua Xu; Lin Shi; He Xiong; Nianjie Feng (Food Research International, 2023)

Effect of protein-glutaminase on the texture, rheology, microstructure and sensory properties of skimmed set-type yoghurt - Jiajing Wu; Tian Dai; Rongyu Lin; Jinjin Niu; Zhen Li; Zhongyi Chang; Caifeng Jia; Chunjing Zou; Deming Jiang; Mingfei Jin; Jing Huang; Hongliang Gao (Food Chemistry, 2023)

The behavior of whey protein isolate-curcumin complex at the oil-water interface - Huanqing Lei; Jiawei Lin; Zeling Chen; Zenan Shi; Debao Niu; Xinan Zeng; Lin Zhou; Zhong Han (Food Hydrocolloids, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Estimate of soil heavy metal in a mining region using PCC-SVM-RFECV-AdaBoost combined with reflectance spectroscopy - Yueyue Wang; Ruiqing Niu; Guo Lin; Yingxu Xiao; Hangling Ma; Lingran Zhao (Environmental Geochemistry and Health, 2023)

Pembrolizumab for the treatment of progressive multifocal leukoencephalopathy in China - Siyuan Fan; Mange Liu; Lin Bai; Sixian Chen; Bo Hou; Nan Lin; Jing Yuan; Chenhui Mao; Jingwen Niu; Haitao Ren; Yanhuan Zhao; Zaiqiang Zhang; et al. (Journal of NeuroVirology, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Impact of inherent calcium in coal on the structure and performance of activated carbon in flue gas activation: The enhanced mechanism of calcite on the methylene blue adsorption - Jian Niu; Lin Luo; Jinglei Cui; Huirong Zhang; Yanxia Guo; Linbo Li; Fangqin Cheng (Journal of Cleaner Production, 2023)

Chemical characteristics of fine tire wear particles generated on a tire simulator - Quanyou Guo; Zhengyu Men; Zhenguo Liu; Zhihui Niu; Tiange Fang; Fengyang Liu; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

Development of a trace quantitative method to investigate caffeine distribution in the Yellow and Bohai Seas, China, and assessment of its potential neurotoxic effect on fish larvae - Zhi Yan; Yaxi Li; Ainuo Lin; Xiao Yang; Zhen Lu; Huilin Zhang; Jianhui Tang; Jianmin Zhao; Donglei Niu; Tianyu Zhang; Xiaodong Zhao; Ke Li (Marine Pollution Bulletin, 2023)

Phototransformation of phosphite induced by zinc oxide nanoparticles (ZnO NPs) in aquatic environments - Qiang Liu; Xiaojun Niu; Dongqing Zhang; Xingyao Ye; Peibing Tan; Ting Shu; Zhang Lin (Water Research, 2023)

Influence of hydrodynamic conditions on the fate of halogenated flame retardants along salinity gradients in a highly polluted micro-tidal estuary - Lin Liu; Yanfang Li; Jian Zhang; Donglei Niu; Jiakai Wang; Jianhui Tang (Science of The Total Environment, 2023)

Strategies for cost-effective remediation of widespread oil-contaminated soils in Kuwait, an environmental legacy of the first Gulf War - Hamad Al-Mebayedh; Anyi Niu; Chuxia Lin (Journal of Environmental Management, 2023)

Three-dimensional porous adsorbent based on chitosan-alginate-cellulose sponge for selective and efficient removal of anionic dyes - Zeng Wen; Die Gao; Hong Niu; Jing Lin; Zhou Li; Jia Zeng; Famin Ke; Kailian Zhang; Zhining Xia; Dandan Wang (Journal of Environmental Chemical Engineering, 2023)

Asymmetric wettable three-dimensional Janus all-cellulose aerogel: Controllable construction with a similar phase self-assembling strategy and oil-water separation performance - Jingjing Zhang; Congcong Wang; Zhibo Lin; Qian Fu; Chenxi Niu; Zaowen Zhao; Lingbin Lu (Journal of Environmental Chemical Engineering, 2023)

Oat bran prevents high-fat-diet induced muscular dysfunction, systemic inflammation and oxidative stress through reconstructing gut microbiome and circulating metabolome - Rui Dong; Kejie Peng; Lin Shi; Qianwen Niu; Hamad Rafique; Yuan Liu; Li Yuan; Liang Zou; Lu Li; Maria Cristina Messia; Xinzhong Hu (Food Research International, 2023)

Supplemental irrigation at the jointing stage of late sown winter wheat for increased production and water use efficiency - Sen Wang; Yuxi Niu; Li Shang; Zhenyan Li; Xiang Lin; Dong Wang (Field Crops Research, 2023)

Load extraction from actual operation data for data-driven ultra-short-term room air-conditioning load prediction - Zhe Tian; Wenjie Song; Yakai Lu; Xinyi Lin; Jide Niu (Energy and Buildings, 2023)

High-strength, self-reinforcing and recyclable multifunctional lignin-based polyurethanes based on multi-level dynamic cross-linking - Zhiyi Huang; Huan Wang; Jiahao Du; Xiaochun Liu; Guoyi Pan; Xingshan Yin; Wenjing Lin; Xiaofeng Lin; Yingjuan Sun; Guobin Yi; Li Niu (Chemical Engineering Journal, 2023)

Novel ternary Cu0-coupled core-shell Fe0/C nanoparticles micro-electrolysis system toward degradation of organic pollutants: Synergistic effects and removal mechanism - Lin Niu; Xiaoli Zhao; Zhi Tang; Yaqi Cai; Qitao Lei; Deyi Hou; Hongyun Niu; Liangjie Wang; John P. Giesy; Fengchang Wu (Science of The Total Environment, 2023)

Water use strategy of nitraria tangutorum shrubs in ecological water delivery area of the lower inland river: Based on stable isotope data - Dongdong Qiu; Guofeng Zhu; Mohd Aadil Bhat; Lei Wang; Yuwei Liu; Liyuan Sang; Xinrui Lin; Wenhao Zhang; Niu Sun (Journal of Hydrology, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Therapy of spinal cord injury by zinc pyrogallol modified nanozyme via anti-inflammatory strategies - Wenxin Chen; Sen Lin; Yanfeng Shi; Qiang Guo; Yuanhong Xu; Yusheng Niu (Chemical Engineering Journal, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

Evolutionary roles of polyploidization‐derived structural variations in the phenotypic diversification of Panax species - Yu‐Xin Zhang; Xin‐Feng Wang; Yu‐Qian Niu; Yu‐Guo Wang; Wen‐Ju Zhang; Zhi‐Ping Song; Ji Yang; Lin‐Feng Li (Molecular Ecology, 2023)
Genomic structural variations (SVs) are widespread in plant and animal genomes and play important roles in phenotypic novelty and species adaptation. Frequent whole genome duplications followed by (re)diploidizations have resulted in high diversity of genome architecture among extant species. In this study, we identified abundant genomic SVs in the Panax genus that are hypothesized to have occurred through during the repeated polyploidizations/(re)diploidizations. Our genome‐wide comparisons demonstrated that although these polyploidization‐derived SVs have evolved at distinct evolutionary stages, a large number of SV‐intersecting genes showed enrichment in functionally important pathways related to secondary metabolites, photosynthesis and basic cellular activities. In line with these observations, our metabolic analyses of these Panax species revealed high diversity of primary and secondary metabolites both at the tissue and interspecific levels. In particular, genomic SVs identified at ginsenoside biosynthesis genes, including copy number variation and large fragment deletion, appear to have played important roles in the evolution and diversification of ginsenosides. A further herbivore deterrence experiment demonstrated that, as major triterpenoidal saponins found exclusively in Panax , ginsenosides provide protection against insect herbivores. Our study provides new insights on how polyploidization‐derived SVs have contributed to phenotypic novelty and plant adaptation.

Risk assessment of predatory lady beetle Propylea japonica's multi-generational exposure to three non-insecticidal agrochemicals - Guofeng Chang; Hui Xue; Jichao Ji; Li Wang; Xiangzhen Zhu; Kaixin Zhang; Dongyang Li; Xueke Gao; Lin Niu; Mengxue Gao; Junyu Luo; Jinjie Cui (Science of The Total Environment, 2023)

Inhalable mixture of polycyclic aromatic hydrocarbons and metals, DNA oxidative stress and nasal ribosomal DNA copy number amplification: Direct and indirect effect analyses among population - Yanhua Wang; Tao Meng; Liya Zhang; Yang Lin; Nan Wu; Huige Yuan; Zhizhou He; Yong Niu; Yufei Dai; Xing Zhao; Huawei Duan (Journal of Hazardous Materials, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Occurrence and migration of organophosphite and organophosphate esters into food simulants from single-use food packaging in China - Ruize Zhou; Jianqiang Geng; Jie Jiang; Li Lin; Jing Zhang; Yunjia Yang; Xiaojun Wang; Yumin Niu; Bing Shao (Environmental Pollution, 2023)

Effects of climate change on long-term building heating performance of medium-deep borehole heat exchanger coupled heat pump - Sheng Zhang; Jun Liu; Xia Zhang; Dun Niu; Fenghao Wang; Jiale Chai; Yalin Lu; Yongjun Sun; Zhang Lin (Energy and Buildings, 2023)

Combined effects of oxytetracycline concentration and organic loading rate on semi-continuous anaerobic digestion of swine wastewater - Zhiwei Huang; Qiuya Niu; Wenkai Nie; Yan Lin; Shaohua Wu; Xiang Li; Jay J. Cheng; Chunping Yang (Bioresource Technology, 2023)

GNSS position-aided delay-locked loops for accurate urban navigation - Tisheng Zhang; Jinwei Shi; Tao Lin; Xin Feng; Xiaoji Niu (GPS Solutions, 2023)

Dynamic soil arching in piled embankment under train load of high-speed railways - Tingting Niu; Yule Yang; Qianli Ma; Jiuqun Zou; Bin Lin (Earthquake Engineering and Engineering Vibration, 2023)

Transcriptional repressor AGL79 positively regulates flowering time in Arabidopsis - Haibo Yang; Pengcheng Zhang; Diandian Guo; Na Wang; Hao Lin; Xingchun Wang; Lifang Niu (Journal of Plant Physiology, 2023)

Atrazine exposure can dysregulate the immune system and increase the susceptibility against pathogens in honeybees in a dose-dependent manner - Kang Wang; Minqi Cai; Jie Sun; Heng Chen; Zheguang Lin; Zhi Wang; Qingsheng Niu; Ting Ji (Journal of Hazardous Materials, 2023)

Sodium alginate/chitosan-based intelligent bilayer film with antimicrobial activity for pork preservation and freshness monitoring - Shenghui Cao; Shuo Wang; Qingqing Wang; Gang Lin; Baolong Niu; Ruijie Guo; Hong Yan; Huifang Wang (Food Control, 2023)

Biochars-Fe PCu hybrides deriving from solid waste and waste acids for elimination of refractory organic pollutants from pharmaceutical wastewater - Huiwen Jin; Li Li; Na Luo; Hongyun Niu; Jinglong Han; Lin Xu; Zhineng Hao; Dong Cao; Yaqi Cai (Chemical Engineering Journal, 2023)

Identifying gaps in the ex situ conservation of native plant diversity in China - Jianfei Ye; Zhangjian Shan; Danxiao Peng; Miao Sun; Yanting Niu; Yun Liu; Qian Zhang; Yong Yang; Qinwen Lin; Jin Chen; Renbin Zhu; Yingwei Wang; et al. (Biological Conservation, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Occurrence, Degradation Pathways, and Potential Synergistic Degradation Mechanism of Microplastics in Surface Water: A Review - Lihua Niu; Yingjie Wang; Yi Li; Li Lin; Yamei Chen; Jiayan Shen (Current Pollution Reports, 2023)

Antifungal activity of ginsenoside CK against Botrytis cinerea by targeting sterol 14α-demethylase cytochrome P450 (CYP51) and the application on cherry tomato preservation - Xiaodi Niu; Xuehui Duan; Siwen Lyu; Lu Liu; Li Lin; Yiding Yu; Hongsu Wang (Postharvest Biology and Technology, 2023)

Imbalanced data-oriented model learning method for ultra-short-term air conditioning load prediction - Zhe Tian; Xinyi Lin; Yakai Lu; Wenjie Song; Jide Niu (Energy and Buildings, 2023)

In-situ gastritis diagnosis by an oral-administration NIR fluorescent probe with a large Stokes shift and high signal-to-noise ratio - Yanyan Ma; Jie Niu; Xing Liang; Lin Wang; Yimeng Zhang; Hongmin Lv; Tao Wang; Jing Wang; Xiaonan Zhang; Shanshan Xu; Qing Zhu; Zike Jiang; et al. (Chemical Engineering Journal, 2023)

Triple-enzyme-mimicking AuPt3Cu hetero-structural alloy nanozymes towards cascade reactions in chemodynamic therapy - Lin Li; Yuanyuan Hu; Yuhe Shi; Yang Liu; Tianqi Liu; Huiwen Zhou; Wenxin Niu; Ling Zhang; Jiaheng Zhang; Guobao Xu (Chemical Engineering Journal, 2023)

Chemiluminescence Immunoassay Method of Urinary Liver Fatty-acid-binding Protein as a Promising Candidate for Kidney Disease - Lisong Niu; Lanya Li; Jinshan Li; Zhitian Chen; Jiayuan Lin; Bo Zhang; Xiaoling Fu (Journal of Fluorescence, 2023)

FexO4-enhanced degradation of bisphenol A in visible light/peroxydisulfate system: production of singlet state oxygen - Zhimin Xu; Shaohua Ju; Peng Gao; Junjian Lin; Yifan Niu; Fei Meng; Shunling Li; Fangfang Li; Jiahao Du; Li Xu; Hongbo Peng; Bo Pan (Environmental Science and Pollution Research, 2023)

The third peak structure in the double J / ψ spectrum - Peng-Yu Niu; Zhenyu Zhang; Qian Wang; Meng-Lin Du (Science Bulletin, 2023)

Impact of primary emission variations on secondary inorganic aerosol formation: Prospective from COVID-19 lockdown in a typical northern China city - Xiaolin Duan; Yulong Yan; Kai Xie; Yueyuan Niu; Yang Xu; Lin Peng (Environmental Pollution, 2023)

Performance of Sludge in the UASB Reactor for Treating Sulfate Wastewater: Sulfate Removal and Changes in the Community Structure Before and After Reaction - Liping Niu; Shuang Sun; Fangying Yu; Xinyue Zhang; Shiying Fan; Yue Sun; Wenlong Lin; Bowen Wang; Xingde Zhang (Water, Air, & Soil Pollution, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Spatiotemporal analysis and prediction of water quality in Pearl River, China, using multivariate statistical techniques and data-driven model - HaoNan Ding; Xiaojun Niu; Dongqing Zhang; Mengyu Lv; Yang Zhang; Zhang Lin; Mingli Fu (Environmental Science and Pollution Research, 2023)

Empirical research on household consumption carbon emissions and key impact factors in urban and rural China - Yinghuan Lian; Xiangyi Lin; Hongyun Luo; Yi Niu; Jianhua Zhang (Environmental Science and Pollution Research, 2023)

A novel BC/g-C3N4 porous hydrogel carrier used in intimately coupled photocatalysis and biodegradation system for efficient removal of tetracycline hydrochloride in water - Huanjun Zhang; Yanan Yu; Yi Li; Li Lin; Chi Zhang; Wenlong Zhang; Longfei Wang; Lihua Niu (Chemosphere, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

The novel chitosan-amphoteric starch dual flocculants for enhanced removal of Microcystis aeruginosa and algal organic matter - Jingshu Cui; Xiaojun Niu; Dongqing Zhang; Jinling Ma; Xifen Zhu; Xiaoxian Zheng; Zhang Lin; Mingli Fu (Carbohydrate Polymers, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

A pH- and enzymatic-responsive nanopesticide to control pea aphids and reduce toxicity for earthworms - Xuqian Zhang; Ying He; Zitong Yuan; Guangmao Shen; Zan Zhang; Jinzhi Niu; Lin He; Jinjun Wang; Kun Qian (Science of The Total Environment, 2023)

Water quality criteria and ecological risk assessment of lead (Pb) in China considering the total hardness of surface water: A national-scale study - Weigang Liang; Xiaolei Wang; Xiao Zhang; Lin Niu; Junyu Wang; Xia Wang; Xiaoli Zhao (Science of The Total Environment, 2023)

Two new pentasaccharide resin glycosides from Argyreia acuta - Yi-Lin Niu; Zhi-Tong Li; Yong-Qin Yin (Phytochemistry Letters, 2023)

A label-free PEC aptasensor platform based on g-C3N4/BiVO4 heterojunction for tetracycline detection in food analysis - Zhengzheng Zhao; Zhifang Wu; Xueling Lin; Fangjie Han; Zhishan Liang; Likun Huang; Mengjiao Dai; Dongxue Han; Lipeng Han; Li Niu (Food Chemistry, 2023)

Fir sawdust as a low-cost and easily recyclable adsorbent: efficient removal of Pb(II), Cu(II), and Zn(II) contaminants from wastewater - Gang Zhou; Shuailong Li; Chenxi Niu; Qi Wang; Xinyuan Zhang; Qunzhi Meng; Lin Li (Environmental Science and Pollution Research, 2023)

Effects of synthetic astaxanthin and Haematococcus pluvialis on growth, antioxidant capacity, immune response, and hepato-morphology of Oncorhynchus mykiss under cage culture with flowing freshwater - Wei Zhao; Han-Lin Wei; Meng-Die Chen; Rong Yao; Zi-Qiao Wang; Jin Niu (Aquaculture, 2023)

Factors affecting N2O fluxes from heavy metal-contaminated mangrove soils in a subtropical estuary - Jiaojiao Ma; Anyi Niu; Zhenni Liao; Junhao Qin; Songjun Xu; Chuxia Lin (Marine Pollution Bulletin, 2023)

Constructing self-assembled microtubular structured Zn–In–S and modulation mechanism towards efficient photocatalytic degradation of tetracycline - Xiaoman Li; Xiaolan Guo; Jiliang Niu; Jialiang Lin; Jianhua Cheng; Yongyou Hu; Yuancai Chen; Weiqiu Wen (Journal of Cleaner Production, 2023)

Optimizing carbon emission forecast for modelling China's 2030 provincial carbon emission quota allocation - Xing Zhou; Anyi Niu; Chuxia Lin (Journal of Environmental Management, 2023)

Nature-inspired 3D hierarchical structured “vine” for efficient microwave attenuation and electromagnetic energy conversion device - Qiangqiang Wang; Ben Niu; Yuhang Han; Qi Zheng; Lin Li; Maosheng Cao (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Physiological equivalent temperature-based and universal thermal climate index-based adaptive-rational outdoor thermal comfort models - Sheng Zhang; Xia Zhang; Dun Niu; Zhaosong Fang; Han Chang; Zhang Lin (Building and Environment, 2023)

Transgenic Bt cotton expressing Cry1Ac/1Ab does not have detrimental effects on the predator Arma chinensis through its prey Helicoverpa armigera - Yamin Ma; Meng Zhang; Junyu Luo; Jichao Ji; Xiangzhen Zhu; Li Wang; Kaixin Zhang; Dongyang Li; Jinjie Cui; Lin Niu (Journal of Pest Science, 2023)

miR-200a-3p Regulates PRKACB and Participates in Aluminium-Induced Tau Phosphorylation in PC12 Cells - Huan Li; Qun Liu; Qinli Zhang; Xingli Xue; Jingsi Zhang; Jing Zhang; Li Lin; Qiao Niu (Neurotoxicity Research, 2022)
Aluminium (Al) is an environmental neurotoxin that humans are widely exposed to, but the molecular mechanism of its toxic effects is not fully understood. Many studies have shown that exposure to Al can cause abnormal phosphorylation of the tau protein that is believed as one of pathological features of Alzheimer’s disease. Increasing evidence indicates that microRNAs (miRNAs) may be involved in the pathological processes of neurodegenerative diseases and are potential regulatory factors for related target genes. Phosphorylation at Ser-133 of cAMP response element-binding protein (CREB) is one of the major pathways of CREB activation, and phosphorylation at this site is controlled by protein kinase A (PKA). The catalytic subunit of PKA, cAMP-dependent protein kinase catalytic subunit beta (PRKACB), phosphorylates CREB. The target gene prediction software TargetScan showed that PRKACB was one of the target mRNAs of miR-200a-3p. The purpose of this study was to investigate whether miR-200a-3p regulates the PKA/CREB pathway by targeting PRKACB and leads to abnormal phosphorylation of the tau protein in nerve cells. The results showed that Al exposure increased the expression level of miR-200a-3p, and miR-200a-3p increased the expression of targeted downregulated PRKACB, and then decreased the PKA/CREB signalling pathway activity, leading to abnormal hyperphosphorylation of tau. Graphical Abstract

Failure mode and genesis of bare dispersive soil slope in the cold dry region: insights from Southwest Songnen Plain, China - Yan Han; Qing Wang; Cencen Niu; Huicheng Fu; Jing Liu; Mengxia Han; Sen Lin; Muhammad Ammar (Bulletin of Engineering Geology and the Environment, 2022)

Important But Overlooked Potential Risks of Substituted Polycyclic Aromatic Hydrocarbon: Looking Below the Tip of the Iceberg - Xiao Zhang; Xiaolei Wang; Xiaoli Zhao; Zhi Tang; Weigang Liang; Xiaowei Wu; Junyu Wang; Xia Wang; Lin Niu (Reviews of Environmental Contamination and Toxicology, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Plasma Lipidomic Subclasses and Risk of Hypertension in Middle-Aged and Elderly Chinese - Zhenhua Niu; Qingqing Wu; Yaogan Luo; Di Wang; He Zheng; Yanpu Wu; Xiaowei Yang; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2022)

Variations of suspended sediment transport caused by changes in shoreline and bathymetry in the Zhujiang (Pearl) River Estuary in the wet season - Shicheng Lin; Jianwei Niu; Guangping Liu; Xing Wei; Shuqun Cai (Acta Oceanologica Sinica, 2022)

Prognostic implication and immunotherapy response prediction of a costimulatory molecule signature in kidney renal clear cell carcinoma - Gaoteng Lin; Yuanyuan Yang; Qingfu Feng; Fangfang Zhan; Chuangxin Sun; Yuanjie Niu; Gang Li (Immunogenetics, 2022)

Review of the formation and influencing factors of food-derived glycated lipids - Lipeng Han; Qingna Lin; Guoqin Liu; Dongxue Han; Li Niu (Critical Reviews in Food Science and Nutrition, 2022)

X-ray Irradiation Improves Neurological Function Recovery of Injured Spinal Cord by Inhibiting Inflammation and Glial Scar Formation - Yi Wang; Yanping Niu; Fanguo Lin; Peng Su; Liesong Chen; Dong Liu; Yongming Sun (Journal of Molecular Neuroscience, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Association of genetic polymorphisms of VAX1, MAFB, and NTN1 with nonsyndromic cleft lip with or without cleft palate in Chinese population - Li Peng; Zhenmin Niu; Jiapei Chen; Teng Wan; Dandan Wu; Yusheng Yang; Guomin Wang; Lin Yang; Wei Huang; Zhenqi Chen (Molecular Genetics and Genomics, 2022)

Correction to: Stenotrophomonas nematodicola sp. nov., isolated from Caenorhabditis elegans - Xuyang Wei; Shengwei Lei; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2022)

Effectiveness of cascading time series models based on meteorological factors in improving health risk prediction - Shuopeng Jia; Weibin She; Zhipeng Pi; Buying Niu; Jinhua Zhang; Xihan Lin; Mingjun Xu; Weiya She; Jun Liao (Environmental Science and Pollution Research, 2022)

Stenotrophomonas nematodicola sp. nov., isolated from Caenorhabditis elegans - Xuyang Wei; Shengwei Lei; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2021)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Stenotrophomonas strain CPCC 101271, an intestinal lifespan-prolonging bacterium for Caenorhabditis elegans that assists in host resistance to “Bacillus nematocida” colonization - Rui Han; Yu Wang; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2021)
The soil-dwelling, opportunistic pathogenic bacterium "Bacillus nematocida" B16 exhibits strong killing activities against a variety of pathogenic nematodes via a “Trojan horse” mechanism that can kill worm species like Caenorhabditis elegans . The bacterial strain CPCC 101271 was previously isolated from the intestines of C. elegans that were recovered from natural habitats and can serve as a probiotic for C. elegans , while also assisting in resistance to infection by the pathogenic strain B16. In this study, the lifespan of C. elegans fed with strain CPCC 101271 cells was extended by approximately 40% compared with that of worms fed with Escherichia coli OP50 cells. In addition, the colonization of C. elegans by the pathogenic bacterium "B. nematocida" B16 was inhibited when pre-fed with strain CPCC 101271. Metagenomic sequence analysis of intestinal microbiota of C. elegans fed with strain CPCC 101271 and infected with B16 revealed that pre-feeding worms with CPCC 101271 improved the diversity of the intestinal bacteria. Moreover, community structure significantly varied in coordination with Stenotrophomonas spp. and Bacillus spp. abundances when competition between strains CPCC 101271 and B16 was evaluated. In conclusion, the nematode microbiota strain CPCC 101271 assisted in its host resistance to colonization by the pathogen "Bacillus nematocida" and can also promote life span-prolongation in C. elegans. These results underscore that understanding the interactions between C. elegans microbiota and pathogens can provide new insights into achieving effective biological control of agricultural pests.

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

The developmental regulator PatD modulates assembly of the cell‐division protein FtsZ in the cyanobacterium Anabaena sp. PCC 7120 - Li Wang; Tian‐Cai Niu; Ana Valladares; Gui‐Ming Lin; Ju‐Yuan Zhang; Antonia Herrero; Wen‐Li Chen; Cheng‐Cai Zhang (Environmental Microbiology, 2021)
Summary FtsZ is a tubulin‐like GTPase that polymerizes to initiate the process of cell division in bacteria. Heterocysts are terminally differentiated cells of filamentous cyanobacteria that have lost the capacity for cell division and in which the ftsZ gene is downregulated. However, mechanisms of FtsZ regulation during heterocyst differentiation have been scarcely investigated. The patD gene is NtcA dependent and involved in the optimization of heterocyst frequency in Anabaena sp. PCC 7120. Here, we report that the inactivation of patD caused the formation of multiple FtsZ‐rings in vegetative cells, cell enlargement, and the retention of peptidoglycan synthesis activity in heterocysts, whereas its ectopic expression resulted in aberrant FtsZ polymerization and cell division. PatD interacted with FtsZ, increased FtsZ precipitation in sedimentation assays, and promoted the formation of thick straight FtsZ bundles that differ from the toroidal aggregates formed by FtsZ alone. These results suggest that in the differentiating heterocysts, PatD interferes with the assembly of FtsZ. We propose that in Anabaena FtsZ is a bifunctional protein involved in both vegetative cell division and regulation of heterocyst differentiation. In the differentiating cells PatD‐FtsZ interactions appear to set an FtsZ activity that is insufficient for cell division but optimal to foster differentiation.

Machine learning-based thermokarst landslide susceptibility modeling across the permafrost region on the Qinghai-Tibet Plateau - Guoan Yin; Jing Luo; Fujun Niu; Zhanju Lin; Minghao Liu (Landslides, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Seed blends of pyramided Cry/Vip maize reduce Helicoverpa zea populations from refuge ears - Jianguo Guo; Isaac Oyediran; Marlin E. Rice; Sebe Brown; Marcelo Dimase; Shucong Lin; Wade Walker; Wenbo Yu; Ying Niu; Fangneng Huang (Journal of Pest Science, 2021)

Trueperella pyogenes pyolysin inhibits lipopolysaccharide-induced inflammatory response in endometrium stromal cells via autophagy- and ATF6-dependent mechanism - Maozhen Qi; Jianguo Liu; Qingran Jiang; Hongyu Niu; Xinyu Wang; Dong Zhou; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin (Brazilian Journal of Microbiology, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Air-pollutant mass concentration changes during COVID-19 pandemic in Shanghai, China - Zhi Niu; Tingting Hu; Lin Kong; Wenqi Zhang; Pinhua Rao; Dafeng Ge; Mengge Zhou; Yuseng Duan (Air Quality, Atmosphere & Health, 2021)

Formation and driving factors of sulfate in PM2.5 at a high-level atmospheric SO2 city of Yangquan in China - Cheng Wang; Yulong Yan; Yueyuan Niu; Rumei Li; Yang Xu; Dongmei Hu; Jing Wu; Lin Peng (Air Quality, Atmosphere & Health, 2021)

sgRNACNN: identifying sgRNA on-target activity in four crops using ensembles of convolutional neural networks - Mengting Niu; Yuan Lin; Quan Zou (Plant Molecular Biology, 2021)

The Biomechanical Response of the Lower Cervical Spine Post Laminectomy: Geometrically-Parametric Patient-Specific Finite Element Analyses - Mohammad Nikkhoo; Chih-Hsiu Cheng; Jaw-Lin Wang; Chi-Chien Niu; Mohamad Parnianpour; Kinda Khalaf (Journal of Medical and Biological Engineering, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Modeling motor task activation from resting-state fMRI using machine learning in individual subjects - Chen Niu; Alexander D. Cohen; Xin Wen; Ziyi Chen; Pan Lin; Xin Liu; Bjoern H. Menze; Benedikt Wiestler; Yang Wang; Ming Zhang (Brain Imaging and Behavior, 2021)

Application of solid-phase extraction based on magnetic nanoparticle adsorbents for the analysis of selected persistent organic pollutants in environmental water: A review of recent advances - Aiming Wu; Xiaoli Zhao; Junyu Wang; Zhi Tang; Tianhui Zhao; Lin Niu; Wenqiang Yu; Chunyan Yang; Mengyuan Fang; Hongzhou Lv; Shasha Liu; Fengchang Wu (Critical Reviews in Environmental Science and Technology, 2021)

Rockburst Risk Analysis During High-Hard Roof Breaking in Deep Mines - Qiming Zhang; Enyuan Wang; Xiaojun Feng; Yue Niu; Muhammad Ali; Song Lin; Hao Wang (Natural Resources Research, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Benzophenanthridine alkaloids suppress lung adenocarcinoma by blocking TMEM16A Ca2+-activated Cl− channels - Gaohua Zhang; Lin Zhu; Yucong Xue; Zhijun Zhao; Honglin Li; Zhiyun Niu; Xiangchong Wang; Pingping Chen; Jianping Zhang; Xuan Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

Strain-softening composite damage model of rock under thermal environment - Wen-lin Feng; Chun-sheng Qiao; Tan Wang; Ming-yuan Yu; Shuang-jian Niu; Zi-qi Jia (Bulletin of Engineering Geology and the Environment, 2020)

Rapid and accurate initial alignment of the low-cost MEMS IMU chip dedicated for tilted RTK receiver - Qijin Chen; Huan Lin; Ruonan Guo; Xiaoji Niu (GPS Solutions, 2020)

Noninvasive ultrasound deep brain stimulation of nucleus accumbens induces behavioral avoidance - Lili Niu; Yanchen Guo; Zhengrong Lin; Zhe Shi; Tianyuan Bian; Lin Qi; Long Meng; Anthony A. Grace; Hairong Zheng; Ti-Fei Yuan (Science China Life Sciences, 2020)

A novel peroxiredoxin from the antagonistic endophytic bacterium Enterobacter sp. V1 contributes to cotton resistance against Verticillium dahliae - Lin Zhang; Ye Tao; Suya Zhao; Xiaoyan Yin; Junmei Chen; Miao Wang; Yingfan Cai; Qiuhong Niu (Plant and Soil, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

An Improved Strain-Softening Damage Model of Rocks Considering Compaction Nonlinearity and Residual Stress Under Uniaxial Condition - Wen-lin Feng; Chun-sheng Qiao; Shuang-jian Niu; Zi-qi Jia (Geotechnical and Geological Engineering, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Macro-mechanical properties of saturated sandstone of Jushan Mine under post-peak cyclic loading: an experimental study - Wen-lin Feng; Chun-sheng Qiao; Shuang-jian Niu; Ming-yuan Yu; Zi-qi Jia (Arabian Journal of Geosciences, 2019)

Fluorescence Imaging of Mitochondria with Three Different Sets of Signals Based on Fluorene Cation Fluorescent Probe - Weishan Wang; Yong Liu; Jie Niu; Weiying Lin (Journal of Fluorescence, 2019)

Field study on the use of gravelly tunnel muck for frost heave and thaw settlement prevention in soft subgrades, northwest China - Libo Wu; Fujun Niu; Zhanju Lin; Jing Luo (Arabian Journal of Geosciences, 2019)

Correction to: Occurrence of polybrominated diphenyl ethers in floor and elevated surface house dust from Shanghai, China - Dong Niu; Yanling Qiu; Li Li; Yihui Zhou; Xinyu Du; Zhiliang Zhu; Ling Chen; Zhifen Lin (Environmental Science and Pollution Research, 2019)

Antioxidant vitamin E protects embryos of Xenopus tropicalis against lambda-cyhalothrin induced embryotoxicity - Lin Jiang; Anyu Chen; Fang Niu; Ying Zhang (Environmental Science and Pollution Research, 2019)

EGFR Mimotope Reduces the Expression of LYVE-1 in the Intestine from the M3R Immunized Mice - Haoran Yuan; Changhong Li; Jianying Niu; Lin Yang (International Journal of Peptide Research and Therapeutics, 2019)

Synthesis and antiphytoviral activity of α-aminophosphonates containing 3, 5-diphenyl-2-isoxazoline as potential papaya ringspot virus inhibitors - Zhi-Gang Zeng; Niu Liu; Fei Lin; Xun-Yuan Jiang; Han-Hong Xu (Molecular Diversity, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Lowest Elevation of Plant Growth and Soil Characteristics in Natural Drawdown Areas in the Jiangjin Section of the Yangtze River - Mingzhi Liu; Yuanyuan Liu; Bo Zeng; Hangang Niu; Songping Liu; Xiaojiao Pan; Jiaojiao Xie; Shaohua Shi; Feng Lin (Wetlands, 2019)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Physiological responses in vitamin C system during hibernation in juvenile Chinese soft-shelled turtle Pelodiscus sinensis - Bojian Chen; Cuijuan Niu; Lin Yuan; Wenyi Zhang (Journal of Oceanology and Limnology, 2019)

Associations between ambient temperature and daily hospital admissions for rheumatic heart disease in Shanghai, China - Yihui Ge; Cong Liu; Yue Niu; Chen Chen; Weibing Wang; Zhijing Lin; Renjie Chen; Jing Cai; Haidong Kan (International Journal of Biometeorology, 2018)

Physiological and anatomical response of foliar silicon application to Dendrocalamus brandisii plantlet leaves under chilling - Hui Zhan; Li-ya Zhang; Lin Deng; Zhao-hui Niu; Mao-biao Li; Chang-ming Wang; Shuguang Wang (Acta Physiologiae Plantarum, 2018)

Spatial heterogeneity of spring phytoplankton in a large tropical reservoir: could mass effect homogenize the heterogeneity by species sorting? - Yang Yang; Haiyu Niu; Lijuan Xiao; Qiuqi Lin; Bo-Ping Han; Luigi Naselli-Flores (Hydrobiologia, 2018)

A study of biochemical route on construction of waste battery ferrite applying for nickel removal - Zhirui Niu; Shaokang Zhang; Lin Zhu (Environmental Science and Pollution Research, 2018)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Occurrence of polybrominated diphenyl ethers in floor and elevated surface house dust from Shanghai, China - Dong Niu; Yanling Qiu; Li Li; Yihui Zhou; Xinyu Du; Zhiliang Zhu; Ling Chen; Zhifen Lin (Environmental Science and Pollution Research, 2018)
House dust is the main source of human exposure to flame retardants by ingestion. This study investigated the occurrence of polybrominated diphenyl ethers (PBDEs) in indoor dust from 22 houses in Shanghai, China. House dust was separately collected from the floor and elevated furnishings surface (mostly between 0.5 and 2 m height) for comparison. The concentrations of ∑ 22 PBDEs ranged from 19.4 to 3280 ng/g (with a geometric mean of 203 ng/g) and from 55.1 to 792 ng/g (with a geometric mean of 166 ng/g) in floor dust (FD) and elevated surface dust (ESD), respectively. BDE-209 was the predominant congener, accounting for about 73.1% of total PBDE burdens. In terms of congener profiles, the comparison of FD and ESD revealed no significant differences except for the ratio of BDE-47/BDE-99. ESD samples displayed a ratio of BDE-47/BDE-99 very similar to commercial penta-BDE products DE-71 while the ratio in FD was exceptionally higher. Significant correlation was found between concentrations of commercial penta-BDE compositions in FD and ESD ( p < 0.05). Except for some occasional values, PBDE levels in house dust exhibited temporal stability. Human exposure to PBDEs via dust ingestion was estimated. The highest daily intake of PBDEs was for toddlers by using 95th percentile concentrations of PBDEs via high dust ingestion in FD (23.07 ng/kg bw/day). About 20-fold difference in exposure estimates between toddlers and adults supports that toddlers are facing greater risk from indoor floor dust. Expectedly, this study highlighted the point that residents in Shanghai were exposed to low doses of PBDEs in house dust.

Early life exposure of zebrafish (Danio rerio) to synthetic pyrethroids and their metabolites: a comparison of phenotypic and behavioral indicators and gene expression involved in the HPT axis and innate immune system - Chao Xu; Xinfang Li; Meiqing Jin; Xiaohui Sun; Lili Niu; Chunmian Lin; Weiping Liu (Environmental Science and Pollution Research, 2018)

Variations in the northern permafrost boundary over the last four decades in the Xidatan region, Qinghai–Tibet Plateau - Jing Luo; Fu-jun Niu; Zhan-ju Lin; Ming-hao Liu; Guo-an Yin (Journal of Mountain Science, 2018)

Root-induced changes to soil water retention in permafrost regions of the Qinghai-Tibet Plateau, China - Zeyong Gao; Fujun Niu; Yibo Wang; Zhanju Lin; Jing Luo; Minghao Liu (Journal of Soils and Sediments, 2018)

Responsibility modulates the neural correlates of regret during the sequential risk-taking task - Lin Li; Zhiyuan Liu; Huanghuang Niu; Li Zheng; Xuemei Cheng; Peng Sun; Fanzhi Anita Zhou; Xiuyan Guo (Experimental Brain Research, 2018)

Characteristics of rock fragments in different forest stony soil and its relationship with macropore characteristics in mountain area, northern China - Chen Meng; Jian-zhi Niu; Zheng-cong Yin; Zi-teng Luo; Xing-na Lin; Jing-wei Jia (Journal of Mountain Science, 2018)

Using circulating tumor cells to evaluate the efficacy of irreversible electroporation for unresectasble pancreatic cancer - Mao Lin; Mohammed Alnaggar; Shu-Zhen Liang; Jian Shi; Li-Zhi Niu; Ji-Bing Chen; Ke-Cheng Xu (Immunologic Research, 2018)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

Identification of heat-responsive miRNAs to reveal the miRNA-mediated regulatory network of heat stress response in Betula luminifera - Ying Pan; Mingyue Niu; Junsheng Liang; Erpei Lin; Zaikang Tong; Junhong Zhang (Trees, 2017)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Quantifying soil macropore networks in different forest communities using industrial computed tomography in a mountainous area of North China - Chen Meng; Jianzhi Niu; Xiang Li; Ziteng Luo; Xiaoqing Du; Jie Du; Xingna Lin; Xinxiao Yu (Journal of Soils and Sediments, 2017)

Clinical efficacy of percutaneous cryoablation combined with allogenic NK cell immunotherapy for advanced non-small cell lung cancer - Mao Lin; Shu-Zhen Liang; Xiao-Hua Wang; Ying-Qing Liang; Ming-Jie Zhang; Li-Zhi Niu; Ji-Bing Chen; Hai-Bo Li; Ke-Cheng Xu (Immunologic Research, 2017)

The improvement of M1 polarization in macrophages by glycopeptide derived from Ganoderma lucidum - Li-Xin Sun; Zhi-Bin Lin; Jie Lu; Wei-Dong Li; Yan-Dong Niu; Yu Sun; Chen-Yang Hu; Guo-Qiang Zhang; Xin-Suo Duan (Immunologic Research, 2017)

Targeted mutagenesis by CRISPR/Cas9 system in the model legume Medicago truncatula - Yingying Meng; Yaling Hou; Hui Wang; Ronghuan Ji; Bin Liu; Jiangqi Wen; Lifang Niu; Hao Lin (Plant Cell Reports, 2017)

Drought stress-induced changes of microRNAs in diploid and autotetraploid Paulownia tomentosa - Xibing Cao; Guoqiang Fan; Lin Cao; Minjie Deng; Zhenli Zhao; Suyan Niu; Zhe Wang; Yuanlong Wang (Genes & Genomics, 2017)

Ten polymorphic microsatellite markers characterized for Schizothorax pseudaksaiensis and applied for population genetic analysis - MING MING BAO; QIONG ZHOU; CONG XIN XIE; LIN GANG CAI; JIAN GONG NIU; HONG LI (Journal of Genetics, 2016)

HSR mechanisms and effects on the spatial structure of regional tourism in China - Degen Wang; Li Wang; Tian Chen; Lin Lu; Yu Niu; August Lew Alan (Journal of Geographical Sciences, 2016)

WSL3, a component of the plastid-encoded plastid RNA polymerase, is essential for early chloroplast development in rice - Liwei Wang; Chunming Wang; Yihua Wang; Mei Niu; Yulong Ren; Kunneng Zhou; Huan Zhang; Qibing Lin; Fuqing Wu; Zhijun Cheng; Jiulin Wang; Xin Zhang; et al. (Plant Molecular Biology, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Modeling and verifying the impact of time delay on INS-aided GNSS PLLs - Tisheng Zhang; Hongping Zhang; Tao Lin; Kunlun Yan; Xiaoji Niu (GPS Solutions, 2016)

The use of chlorogenic acid and its analogues as inhibitors: an investigation of the inhibition of sortase A of Staphylococcus aureus using molecular docking and dynamic simulation - Chongwei Bi; Lin Wang; Xiaodi Niu; Hongjun Cai; Xiaobo Zhong; Xuming Deng; Tiedong Wang; Dacheng Wang (Biotechnology Letters, 2016)

Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - Guo-an Yin; Fu-jun Niu; Zhan-ju Lin; Jing Luo; Ming-hao Liu (Journal of Mountain Science, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Characterization of the whole chloroplast genome sequence of Acer davidii Franch (Aceraceae) - Yun Jia; Jiao Yang; Yan-Ling He; Ying He; Chuan Niu; Lin-Lin Gong; Zhong-Hu Li (Conservation Genetics Resources, 2016)

Unchanged carbon balance driven by equivalent responses of production and respiration to climate change in a mixed‐grass prairie - Xia Xu; Zheng Shi; Xuecheng Chen; Yang Lin; Shuli Niu; Lifen Jiang; Ruiseng Luo; Yiqi Luo (Global Change Biology, 2016)
Responses of grassland carbon (C) cycling to climate change and land use remain a major uncertainty in model prediction of future climate. To explore the impacts of global change on ecosystem C fluxes and the consequent changes in C storage, we have conducted a field experiment with warming (+3 °C), altered precipitation (doubled and halved), and annual clipping at the end of growing seasons in a mixed‐grass prairie in Oklahoma, USA , from 2009 to 2013. Results showed that although ecosystem respiration ( ER ) and gross primary production ( GPP ) negatively responded to warming, net ecosystem exchange of CO 2 ( NEE ) did not significantly change under warming. Doubled precipitation stimulated and halved precipitation suppressed ER and GPP equivalently, with the net outcome being unchanged in NEE . These results indicate that warming and altered precipitation do not necessarily have profound impacts on ecosystem C storage. In addition, we found that clipping enhanced NEE due to a stronger positive response of GPP compared to ER , indicating that clipping could potentially be an effective land practice that could increase C storage. No significant interactions between warming, altered precipitation, and clipping were observed. Meanwhile, we found that belowground net primary production ( BNPP ) in general was sensitive to climate change and land use though no significant changes were found in NPP across treatments. Moreover, negative correlations of the ER / GPP ratio with soil temperature and moisture did not differ across treatments, highlighting the roles of abiotic factors in mediating ecosystem C fluxes in this grassland. Importantly, our results suggest that belowground C cycling (e.g., BNPP ) could respond to climate change with no alterations in ecosystem C storage in the same period.

OsBAK1 is involved in rice resistance to Xanthomonas oryzae pv. oryzae PXO99 - Hualan Liao; Xiaorong Xiao; Xiuqiong Li; Yan Chen; Xiumei Fu; Daozhe Lin; Xiaolei Niu; Yinhua Chen; Chaozu He (Plant Biotechnology Reports, 2016)

Taxonomic Study of the Genus Apalacris Walker (Orthoptera: Catantopidae) - Z M Zheng; L L Lin; Y Niu (Neotropical Entomology, 2016)

Discovery of microRNAs and transcript targets related to witches’ broom disease in Paulownia fortunei by high-throughput sequencing and degradome approach - Suyan Niu; Guoqiang Fan; Minjie Deng; Zhenli Zhao; Enkai Xu; Lin Cao (Molecular Genetics and Genomics, 2016)

Thaw-induced slope failures and stability analyses in permafrost regions of the Qinghai-Tibet Plateau, China - Fujun Niu; Jing Luo; Zhanju Lin; Jianhong Fang; Minghao Liu (Landslides, 2016)

The effect of different feeding rates on growth, feed efficiency and immunity of juvenile Penaeus monodon - Jin Niu; Xu Chen; Yun-Qiang Zhang; Li-Xia Tian; Hei-Zhao Lin; Jun Wang; Yun Wang; Yong-Jian Liu (Aquaculture International, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Combined effect between two functional polymorphisms of SLC6A12 gene is associated with temporal lobe epilepsy - JINGYUN LI; HUA LIN; FENGHE NIU; XILIN ZHU; NING SHEN; XIN WANG; LIPING LI; AIHUA LIU; XIAOPAN WU; WEI SUN; YUPING WANG; YING LIU (Journal of Genetics, 2015)

Effect of combination of nerve fragments with nerve growth factor in autologous epineurium small gap coaptation on peripheral nerve injury repair - Bo Feng; Hua Ma; He Hu; Lan Zhang; Zhi Zhang; Youming Pang; Yongjun Wang; Kecheng Niu; Ligong Lin (Cell and Tissue Banking, 2015)

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area - Guo-Mei Jia; Bao-Lin Zhang; Jun-Tao Niu; Li-Ming Wang; Fang-Qing Chen (Agroforestry Systems, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Long-term thermal regimes of the Qinghai-Tibet Railway embankments in plateau permafrost regions - FuJun Niu; MingHao Liu; GuoDong Cheng; ZhanJu Lin; Jing Luo; GuoAn Yin (Science China Earth Sciences, 2015)

Altered microRNA Expression in Peripheral Blood Mononuclear Cells from Young Patients with Schizophrenia - Hui-min Fan; Xin-yang Sun; Wei Niu; Lin Zhao; Qiao-Li Zhang; Wan-shuai Li; Ai-fang Zhong; Li-yi Zhang; Jim Lu (Journal of Molecular Neuroscience, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

Experimental Warming Increases Seasonal Methane Uptake in an Alpine Meadow on the Tibetan Plateau - Xingwu Lin; Shiping Wang; Yigang Hu; Caiyun Luo; Zhenhua Zhang; Haishan Niu; Zubin Xie (Ecosystems, 2015)

Raltitrexed’s effect on the development of neural tube defects in mice is associated with DNA damage, apoptosis, and proliferation - Yanting Dong; Xiuwei Wang; Jianlin Zhang; Zhen Guan; Lin Xu; Jianhua Wang; Ting Zhang; Bo Niu (Molecular and Cellular Biochemistry, 2015)

Thaw-induced slope failures and susceptibility mapping in permafrost regions of the Qinghai–Tibet Engineering Corridor, China - Fujun Niu; Jing Luo; Zhanju Lin; Minhao Liu; Guoan Yin (Natural Hazards, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Identification of housekeeping genes suitable for gene expression analysis in the pearl mussel, Hyriopsis cumingii, during biomineralization - Zhiyi Bai; Jingyun Lin; Keyi Ma; Guiling Wang; Donghong Niu; Jiale Li (Molecular Genetics and Genomics, 2014)

Detection of intracellular neutral lipid content in the marine microalgae Prorocentrum micans and Phaeodactylum tricornutum using Nile red and BODIPY 505/515 - Songcui Wu; Baoyu Zhang; Aiyou Huang; Li Huan; Linwen He; Apeng Lin; Jianfeng Niu; Guangce Wang (Journal of Applied Phycology, 2014)

Differential proteomic analysis of polyubiquitin-related proteins in chemical hybridization agent-induced wheat (Triticum aestivum L.) male sterility - Hongzhan Liu; Gaisheng Zhang; Wanwan Zhu; William K. K. Wu; Qingsong Ba; Lin Zhang; Longyu Zhang; Na Niu; Shoucai Ma; Junwei Wang (Acta Physiologiae Plantarum, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Genetic association of the P-glycoprotein gene ABCB1 polymorphisms with the risk for steroid-induced osteonecrosis of the femoral head in Chinese population - Yanqiong Zhang; Xiangying Kong; Rongtian Wang; Shangzhu Li; Yanfang Niu; Liuluan Zhu; Weiheng Chen; Na LIN (Molecular Biology Reports, 2014)

Selenium Attenuates High Glucose-Induced ROS/TLR-4 Involved Apoptosis of Rat Cardiomyocyte - Zhong-Wei Liu; Hai-Tao Zhu; Kun-Lun Chen; Chuan Qiu; Kai-Fa Tang; Xiao-Lin Niu (Biological Trace Element Research, 2013)

Selenium Deficiency Is Associated with Endoplasmic Reticulum Stress in a Rat Model of Cardiac Malfunction - Su-Qin Wang; Xiao-Lin Niu; Zhong-Wei Liu; Yan-He Zhu; Deng-Feng Gao (Biological Trace Element Research, 2013)

Genetic phylogeography and maternal lineages of 18 Chinese black goat breeds - Tao Zhong; Qian Jun Zhao; Li Li Niu; Jie Wang; Peng Fei Jin; Wei Zhao; Lin Jie Wang; Li Li; Hong Ping Zhang; Yue Hui Ma (Tropical Animal Health and Production, 2013)

Global and MGMT promoter hypomethylation independently associated with genomic instability of lymphocytes in subjects exposed to high-dose polycyclic aromatic hydrocarbon - Huawei Duan; Zhini He; Junxiang Ma; Bo Zhang; Zhiguo Sheng; Ping Bin; Juan Cheng; Yong Niu; Haiyan Dong; Han Lin; Yufei Dai; Benzhan Zhu; et al. (Archives of Toxicology, 2013)

Geochronology, petrology, and geochemistry of the Yaojiazhuang ultramafic-syenitic complex from the North China Craton - Bin Chen; XiaoLu Niu; ZhiQiang Wang; Lin Gao; Chao Wang (Science China Earth Sciences, 2013)

Selenium Attenuates Adriamycin-Induced Cardiac Dysfunction via Restoring Expression of ATP-Sensitive Potassium Channels in Rats - Zhong-Wei Liu; Xiao-Lin Niu; Kun-Lun Chen; Yu-Jie Xing; Xuan Wang; Chuan Qiu; Deng-Feng Gao (Biological Trace Element Research, 2013)

Identification and characterization of a novel scFv recognizing human and mouse CD133 - Suresh Kumar Swaminathan; Lin Niu; Nate Waldron; Steve Kalscheuer; David M. Zellmer; Michael R. Olin; John R. Ohlfest; Daniel A. Vallera; Jayanth Panyam (Drug Delivery and Translational Research, 2013)

Removal of anionic azo dye from aqueous solution via an adsorption–photosensitized regeneration process on a TiO2 surface - Nan Bao; Yuan Li; Xiao-Hong Yu; Jun-Jian Niu; Guo-Lin Wu; Xiao-Hong Xu (Environmental Science and Pollution Research, 2013)

Effect of active immunization against a recombinant mouse granulocyte-macrophage colony-stimulating factor/somatostatin fusion protein on the growth of mice - Bingbing Wu; Ruili Qi; Bin Li; Taoyan Yuan; Heshan Liu; Jun He; Zhiwei Lin; Weifen Li; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

Study of phenol biodegradation using Bacillus amyloliquefaciens strain WJDB-1 immobilized in alginate–chitosan–alginate (ACA) microcapsules by electrochemical method - Daban Lu; Yan Zhang; Shiquan Niu; Letao Wang; Shaoxiong Lin; Chunming Wang; Weichun Ye; Chunlei Yan (Biodegradation, 2012)

Generation and application of anti-ouabain IgY antibodies - Ming Juan Zhang; Jun Yang; Can Zhan Zhu; Zong Ming Duan; Xiao Lin Niu (Molecular and Cellular Biochemistry, 2011)

Aucubin modulates Bcl-2 family proteins expression and inhibits caspases cascade in H2O2-induced PC12 cells - Hong Yu Xue; Dong Yan Niu; Gui Zhen Gao; Qiu Ye Lin; Li Ji Jin; Yong Ping Xu (Molecular Biology Reports, 2011)

Effect of the C-terminal domains and terminal residues of catalytic domain on enzymatic activity and thermostability of lichenase from Clostridium thermocellum - Dong Niu; Xu-xia Zhou; Tao-yan Yuan; Zhi-wei Lin; Hui Ruan; Wei-fen Li (Biotechnology Letters, 2010)

Coordinated regulation of anthocyanin biosynthesis in Chinese bayberry (Myrica rubra) fruit by a R2R3 MYB transcription factor - Shan-Shan Niu; Chang-Jie Xu; Wang-Shu Zhang; Bo Zhang; Xian Li; Kui Lin-Wang; Ian B. Ferguson; Andrew C. Allan; Kun-Song Chen (Planta, 2010)

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Prediction of interaction between small molecule and enzyme using AdaBoost - Bing Niu; Yuhuan Jin; Lin Lu; Kaiyan Fen; Lei Gu; Zhisong He; Wencong Lu; Yixue Li; Yudong Cai (Molecular Diversity, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Pc4, a putative movement protein of Rice stripe virus, interacts with a type I DnaJ protein and a small Hsp of rice - Lianming Lu; Zhenguo Du; Meiling Qin; Ping Wang; Hanhong Lan; Xiaoqing Niu; Dongsheng Jia; Liyan Xie; Qiying Lin; Lianhui Xie; Zujian Wu (Virus Genes, 2009)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Prediction of compounds’ biological function (metabolic pathways) based on functional group composition - Yu-Dong Cai; Ziliang Qian; Lin Lu; Kai-Yan Feng; Xin Meng; Bing Niu; Guo-Dong Zhao; Wen-Cong Lu (Molecular Diversity, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Strategies and mechanisms of plant virus resistance - Shih-Shun Lin; Rossana Henriques; Hui-Wen Wu; Qi-Wen Niu; Shyi-Dong Yeh; Nam-Hai Chua (Plant Biotechnology Reports, 2007)

Cloning and characterization of a novel Δ12-fatty acid desaturase gene from the tree Sapium sebiferum - Bei Niu; Huaxun Ye; Ying Xu; Shenghua Wang; Peng Chen; Shuming Peng; Yangchao Ou; Lin Tang; Fang Chen (Biotechnology Letters, 2007)

A neutral protease from Bacillus nematocida, another potential virulence factor in the infection against nematodes - Qiuhong Niu; Xiaowei Huang; Lin Zhang; Yunxia Li; Juan Li; Jinkui Yang; Keqin Zhang (Archives of Microbiology, 2006)

Spatial and temporal dynamics of soil organic carbon in reserved desertification area - Shu-lan Cheng; Hua Ouyang; Hai-shan Niu; Lin Wang; Feng Zhang; Jun-qin Gao; Yu-qiang Tian (Chinese Geographical Science, 2004)

Strand Compositional Asymmetries of Nuclear DNA in Eukaryotes - Deng K. Niu; Kui Lin; Da-Yong Zhang (Journal of Molecular Evolution, 2003)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)